Fibrotic microRNAs in the suppression of HSC activation and ECM deposition to facilitate the regression of hepatic fibrosis in zebrafish - Yu-Heng Lai; Mu-Kuang He; Chung-Tsui Huang; Han-Yu Tseng; Tzu-Ching Lin; Ting-Yu Yang; Semon Wu; Guor Mour Her (Journal of Molecular Medicine, 2026)
During liver injury, early pathological changes may go unnoticed, delaying the diagnosis until the disease has advanced to stages such as fibrosis, cirrhosis, or hepatocellular carcinoma. Hepatic fibrosis is a sign of long-term liver injury that leads toward permanent liver damage. It involves the buildup of too much extracellular matrix (ECM) and is activated by hepatic stellate cells (HSCs). The transforming growth factor-β1 (TGF-β1)/SMAD pathway is central to this process, which shows great potential for therapeutic strategies. Therefore, we investigated the therapeutic potential of microRNA (miRNA)-mediated regulation of fibrogenesis by using zebrafish models. A group of fibrosis-related miRNAs was identified and used to generate transgenic zebrafish lines. Fibrosis was induced via doxycycline (DOX)-controlled overexpression of TGF-β1a, and the antifibrotic efficacy of miRNAs was evaluated. Quantitative real-time PCR showed a marked downregulation of the target miRNAs, accompanied by decreased expression of fibrotic markers. Next, we confirmed that TGF-β1a, GREM1, and α-SMA protein levels were decreasing. Histological staining revealed improved liver structure and diminished collagen deposition. These findings indicate that through manipulating the miRNA expressions, we can effectively disrupt TGF-β-induced fibrogenesis, inactivate HSC, inhibit ECM remodeling, and attenuate liver fibrosis, and highlight the potential of miRNA-based therapeutic strategies for early intervention in liver disease. Key messages Establishment of an in vivo model for developing an inducible miRNA expression system in zebrafish. Predicting and evaluating targeted miRNAs that attenuate TGF-β-induced hepatic fibrosis. Elucidate the potential mechanism for fibrosis that may be a strategy for future therapies. Graphical Abstract MicroRNA-mediated modulation attenuates hepatic fibrosis by coordinately suppressing the TGF-β/SMAD signaling pathway, hepatic stellate cell activation, and extracellular matrix deposition. Protein-level validation confirms reduced phosphorylation of Smad2 and decreased expression of key fibrotic markers, including α-SMA, collagen I, and fibronectin. These findings highlight a multi-target regulatory mechanism through which miRNAs exert antifibrotic effects at the systems level.

Interface-decoupled oxygen reduction via atomic Pt–Pd–Co clusters and vacancy-mediated kinetic buffering in a hierarchical carbon-supported multimetallic oxide platform - Yang-Yang Hsu; Ching-Hua Fan; Yu-Lin LEE; Sheng Dai; Kuan-Wen Wang; Nozomu Hiraoka; Hirofumi Ishii; Ting-Shan Chan; Chia-Shing Wu; Guo-Wei Lee; Po-Chun Chen; Tsan-Yao Chen (Chemical Engineering Journal, 2026)

Regulating cation disorder to stabilize oxygen redox in Li-rich DRX cathodes via Fe substitution - Chia-Ching Lin; Péter Udvarhelyi; Hao-Hsiang Chang; Tsung-Yi Chen; Zhenfei Cai; Yu Zhao; Han-Yi Chen; Denis Y.W. Yu (Chemical Engineering Journal, 2026)

Piezo-coupled triboelectric self-powered tactile sensor based on a self-healable polymer for object recognition - Manikandan Venkatesan; Wei-Wen Chen; Yu-Chen Wang; Yung-Chi Hsu; Jayashree Chandrasekar; Hao-Yuan Chen; Shih-Yu Lin; Chia-Jung Cho; Shang-Jui Huang; Ming-An Chung; Wen-Ya Lee; Yu Wen; et al. (Chemical Engineering Journal, 2026)

Correction: Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

A coarse-to-fine machine-learning framework for identifying functional connectivity markers of cognitive impairment in Parkinson’s disease - Chung-Yao Chien; Tsung-Lin Lee; Tien-Yu Lin; Rwei-Ling Yu; Chou-Ching K. Lin (Medical & Biological Engineering & Computing, 2026)

Green synthesized Cu2O/TiO2 nanotube heterojunction for pharmaceutical mineralization and simultaneous hydrogen evolution: mechanistic insight and toxicity assessment - Fang-Yu Liang; Dong-Ni Wu; Wan-Chun Lin; Yi-Ching Lin; Chia-En Tsai; Chia-Hua Lin; Wu-Xing Chen; Chia-Hung Chen; Yen-Ping Peng (Journal of Environmental Management, 2026)

Circular bioprocessing of bovine blood for peptide-based antimicrobial and antibiofilm agents - Gan Huey; Asif Ali Bhat; Bao-Hong Lee; Ming‐Kuei Shih; Li-Jung Yin; You-Lin Tain; Yu-Wei Chen; Yeu-Ching Shi; Chih-Yao Hou (Bioresource Technology, 2026)

Volatile Compounds from Endophytic PGPM Improve Copper Tolerance by Regulating Redox Balance in Cauliflower - Jing-Yu Chen; Tri-Phuong Nguyen; Chih-Cheng Lin; Ching-Han Chang; Hieng-Ming Ting; Ping-Fu Hou; Hao-Jen Huang (Journal of Plant Growth Regulation, 2026)

First complete coding sequence of ovine herpesvirus 2 from a malignant catarrhal fever case of Formosan sambar deer in Taiwan: Genomic characterization and molecular epidemiology - Ruei-Sheng Tsai; Shih-Te Chuang; Hau-You Tzeng; Fong-Yuan Lin; Ching-Yu Tseng; Yi-Chen Chen; Wei-Li Hsu (The Veterinary Journal, 2026)

Dang-Gui-Bu-Xue-Tang triggers GM-CSF and IL-4 secretion corporated with increased amount of Immunoglobulins - Sheng-Teng Huang; Jia-Hau Yen; Yu-Chun Lin; Ming-Ching Kao; Chia-Ju Chuang; Shu-Tuan Chiang; Te-Mao Li (Advances in Traditional Medicine, 2026)

Novel DUAL Z-SCHEME Bi2MoO6/SO3H@g-C3N4/ZnS photocatalyst enhanced by persulfate activation for rapid ofloxacin degradation: Integrated experimental and DFT studies - Imran Nasir Appau Zahir Hussain; Sanjay Ballur Prasanna; Po-Chun Chen; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2026)

Applying the iRIC Morpho2DH model to determine the effectiveness of check dams against debris flows - Zheng-Yi Feng; Philipp Marr; Tien-Chun Hsu; Ping-Hsuan Kuo; Yu-Po Lin; Ming-Chih Chuang; Ching-Mao Huang; Edoardo Carraro; Su-Chin Chen; Chen-Yu Chen; Thomas Glade (Landslides, 2026)

Middle Eocene arc magmatism from Armenia with new insights into tectonic evolution of the Arabia-Eurasia collision zone - Yu-Chin Lin; Kwan-Nang Pang; Ghazar Galoyan; Rafael Melkonyan; Hao-Yang Lee; Ching-Hua Lo; Jin-Hui Yang; Sun-Lin Chung (Lithos, 2026)

Electroanalytical profiling of Escherichia coli using MOFs-modified gold electrode sensing chips and endogenous β-galactosidase - Ching-Yu Lin; Bhuvan Lokesh Marenahalli; Su-Wei Hu; Po-Han Chiu; Yu-Hsuan Chang; Kevin C.-W. Wu; Yu-Sheng Yu; Ningappa Kumara Swamy; Chia-Hung Liu; Yu-Jui Fan (Journal of Water Process Engineering, 2026)

Safety and toxicity assessment of Lactobacillus salivarius AP-32 with Probiotic potential in vivo and in vitro - Yu-Hsuan Chin; Yi-Wen Chen; Yen-Yu Huang; Ching-Min Li; Jia-Hung Lin; Yi-Wei Kuo; Chen-Yu Chen; Yen-Feng Lee; Cian-Dai Ciou; Ko-Chiang Hsia; Shin-Yu Tsai; Hsieh-Hsun Ho (Food and Chemical Toxicology, 2026)

Methotrexate-loaded FeAuGd nanoparticles for synergistic magnetic-hyperthermia and chemotherapy - Kayalvizhi Samuvel Muthiah; Lenin Subramanian; Yen-Lin Chen; Udesh Dhawan; Yu-Chien Lin; Ching-Li Tseng; Ren-Jei Chung (Chemical Engineering Journal, 2026)

Zebrafish Model Reveals Early Electrocardiographic and Molecular Signatures of Doxorubicin-Induced Cardiotoxicity - Zih-Yin Lai; Chi-Ying Lee; Yu-Ching Chiu; Chia-Hung Lin; Chung-Chi Yang; Chia-Chia Ho; Lawrence Yu-Min Liu; Yung-Jen Chuang (Cardiovascular Toxicology, 2026)

Prioritizing key determinants of hematite photocatalysis through structure – Property contour mapping and statistical correlation analysis - TsingHai Wang; Ching-Lung Chen; Wei-Fan Kuan; Wei-Tong Li; Ching-Yao Ke; Tzu-Han Lin; Chung-Yu Guan; Huei-Ru Fuh (Process Safety and Environmental Protection, 2026)

Inhibitory activity of dehulled adlay extrudate against ethanol-induced gastric mucosal injury and stability tests of active indicative components - Ming-Yi Lee; Shih-Min Hsia; Ching-I Lin; Yu-Chia Chang; Yi-Hsiang Liang; Lu-Chi Chan; Ju-Tsui Lin; Yi-Fen Chiang; Wei-Chih Sun; Cheng-Pei Chung (Journal of Cereal Science, 2026)

Improvement of indoor air quality and health effects in COPD patients in a heavy industrial area - Jia Lin Zhang; Yi Ting Chang; Ching Yu Hsiao; Chung-Shin Yuan; Yen-Ping Peng; Da Wei Wu; Huang-Chi Chen; Jia-Yu Kuo; Huai-Lei Juan; Pei-Shih Chen (Environmental Research, 2026)

Metabolomics-based investigation of PFOS-induced molecular perturbations across multiple rat organs - Tzu-Hsin Yen; Sheng-Han Lee; Hao-Jan Liang; Zou-Xiao Huang; Chi-Tsung Chen; Christopher Li; Ching-Yu Lin (Environmental Toxicology and Pharmacology, 2026)

Untargeted lipidomic profiling reveals the effect of hexabromocyclododecane exposure on a branching coral - Chuan-Ho Tang; Ting-Ju Liu; Ching-Yu Lin; Hsing-Hui Li (Aquatic Toxicology, 2026)

Aldehyde dehydrogenase 2 mitigates acrolein-driven ferroptosis to preserve kidney function - Yu-Ming Kuo; Shiu-Dong Chung; Jui-Ting Chang; Hui-Min Yang; Chieh-Chen Lee; Chih-Ching Lin; Hsiang-Tsui Wang (Environmental Pollution, 2026)

Coupled oxygen and nitrogen defect sites in Co-N4-coordinated frameworks facilitate stepwise CO2 methanation - Pin-Yu Liu; Sheng-Xiang Chou; Wei-Tse Sun; Hsin-Han Chen; Cheng-Hung Tsai; Yen-Lin Lai; Yu-Cheng Shao; Chi-Liang Chen; Yu-Ching Huang; Yun-Wei Chiang; Bo-Hong Liu; Chia-Hsin Wang; et al. (Chemical Engineering Journal, 2026)

Spatio-temporal dynamics of fish assemblages at an offshore wind farm and a comparison with mature artificial reefs - Kwang Tsao Shao; Ching Han Chang; Ching Yi Chen; Lin Tai Ho; Yi Ta Shao; Hsin-Chieh Chiang; Wei-Ning Lee; Hsien Ju Tsai; Tien-Yu Huang; Chun-Yu Chang (Frontiers in Marine Science, 2026)
Introduction Offshore wind farms (OWFs) are vital for sustainable energy. The underwater foundations of those wind turbines provide a complex structure that creates new habitats and attracts fishes. However, whether OWFs had the same ecological function as purpose-built artificial reef (AR) and how they alter the original fish community remain unclear. Methods To evaluate the spatial and temporal variations in fish assemblages, we conducted a multi-part investigation at the Formosa Wind Farm, located off the coast of Miaoli County, Taiwan. Temporal changes were assessed through SCUBA surveys at turbine foundations in 2017, 2018, and 2025, with the 2025 data allowing for a direct comparison with the nearby existing artificial reefs. To assess spatial effects, pole-and-line surveys were conducted from Apr to Oct in 2024 and 2025 at varying distances from the turbines. Results Our investigation documented 86 species of reef-associated fishes exclusively within 50 m of turbine foundations; none were caught in the surrounding sandy areas or documented in pervious fishery records. The results demonstrated that fish assemblages around the turbine piles changed successively over the years. Although the species composition in 2025 differed between the OWF and the established AR sites, key ecological metrics such as species richness, diversity, and trophic structures showed no significant differences. Discussion These findings demonstrated that the underwater structure of offshore wind turbines can function as AR, creating novel reef habitats and supporting reef-associated fish community within a finite spatial extent. Overall, OWFs may provide ecological benefits in addition to renewable energy, highlighting their potential role in balancing energy development with marine conservation.

Optical properties of dissolved organic matter play pivotal roles in mediating trace metal forms in a mangrove-dominated tidal estuary - Keisuke Nakayama; Meng-Chi Hung; Chih-Yu Chiu; Sen-Lin Tang; Mei-Li Hsueh; Chin-Ching Wu; I-Hao Hung; Ya-Hsin Liu; Jeng-Wei Tsai (Marine Pollution Bulletin, 2026)

Cu2Te/Au@rGO aerogel as an efficient electrocatalyst for the bimodal electrochemical-colorimetric detection of 4-nitrotoluene - Nandini Nataraj; Agalya Mahalingam; Xinke Liu; Yu-Chien Lin; Ching-Wei Tung; Hsu-Wei Fang; Ren-Jei Chung (Process Safety and Environmental Protection, 2026)

Dibifree, a dietary phytomix, improves glycemic control and adiposity via modulation of the gut–pancreas–adipose–immune axis in type 2 diabetes - Tzu-Yi Huang; Niann-Tzyy Dai; Hsiu-Jung Liao; Ly Hien Doan; Tai-Shan Cheng; Wen-Yu Hsieh; I-Hsuan Lin; Yu-Tang Huang; Chia-Ching Liaw; Hsiao-Sheng Liu; Wei-Ming Cheng; Chun-Li Su; et al. (Food Research International, 2026)

AMPK Activation by ENERGI Ameliorates Behavioral and Synaptic Deficits in a Mouse Model of Autism - Ming-Chia Chu; Chi-Chun Wu; Yueh-Jung Chung; Chieh-Yu Chang; Han-Fang Wu; Sze-Chi Tsai; Tzu-Ning Peng; Tzu-Jung Yang; Hui-Ching Lin (Molecular Neurobiology, 2026)
Autism spectrum disorder (ASD), a neurodevelopmental disorder, is characterized by synaptic dysregulation as its underlying pathophysiological mechanism. AMP-activated protein kinase (AMPK), an intracellular energy sensor, plays a pivotal role in regulating synaptic integrity and function. Current treatments for ASD exhibit limited benefits in alleviating the core symptoms of ASD. Consequently, we investigated the therapeutic potential of ENERGI, a novel AMPK-activating compound, in a valproate (VPA)-induced mouse model of ASD. ENERGI was administered via drinking water to VPA-induced ASD offspring. After 7 days of treatment, ENERGI gradually alleviated social defects, repetitive behaviors, and emotional comorbidities in VPA-induced ASD offspring. At the synaptic level, ENERGI treatment restored aberrant plasticity, spine structure, and dendritic arborization in the hippocampus of VPA-induced ASD offspring. Notably, the curative effects of ENERGI in VPA-induced ASD offspring were equivalent to those of D-cycloserine (DCS), a known therapeutic candidate for ASD. Moreover, ENERGI demonstrated superior efficacy in restoring spine abnormalities than DCS. Mechanistically, 7-day ENERGI treatment reversed the reduction in AMPK phosphorylation, and normalized the elevated PSD95 and synaptic GluA2 levels in VPA-induced ASD offspring, whereas DCS treatment only rescued the synaptic GluA2 levels. Overall, these findings suggest that AMPK activation by ENERGI effectively reverses behavioral and synaptic deficits in a preclinical ASD model, supporting AMPK as a promising target for developing novel ASD therapies.

Emerging trends and clinical challenges in AI-enhanced emotion diagnosis using physiological data - Ying-Ying Tsai; Guan-Lin Wu; Yu-Jie Chen; Yen-Feng Lin; Ju-Yu Wu; Ching-Han Hsu; Lun-De Liao (Medical & Biological Engineering & Computing, 2026)

Strategies for Promoting Sustainable Development of Land and Water Resources in a Land Subsidence Affected Area of Taiwan - Chung‐Feng Ding; Yu‐Ching Lin; Reuy‐Chi Kao (Irrigation and Drainage, 2025)
Land subsidence has been observed in many parts of the world. In Taiwan, the main cause is the excessive extraction of groundwater in alluvial plains. For limited land and water resources, it is essential to balance the development among economics, society and conservation issues in land subsidence‐affected areas. The Taiwan government promotes ‘prevention (non‐engineering)’ and ‘reclamation (engineering)’ strategies since the 1980s, which are to increase surface and alternative water supply, decrease groundwater abstraction, strengthen groundwater recharge, enhance enforcement related to water resources utilization and management, reduce induced disasters and encourage public participation. This paper reports the framework of prevention and reclamation strategies and their relative achievements; furthermore, it recently integrated ICT technology with low‐cost devices to monitor the regional pumping behaviour related to land subsidence for groundwater management. The real‐time monitoring system enables the utilization of groundwater more effectively and sustainably in reducing land subsidence. In 2022, according to the delimited goals of each strategy in every phase, all achievements were effective in mitigating the annual subsiding rate and affected area, the former from over 20 cm/year down to 8 cm/year, the latter from 1616 to 310 km 2 .

Potential anti-H1N1 schitriterpenoids from Kadsura japonica L. vines - Hung-Tse Huang; Chun-Tang Chiou; Yu-Chi Lin; Li-Jie Zhang; Chih-Hua Chao; Ping-Jyun Sung; Jih-Jung Chen; Tsung-Lin Li; I-Wen Lo; Chia-Ching Liaw (Phytochemistry, 2025)

Multifunctional visual photoelectrochemical sensor based on ternary Sb2WO6/P@g-C3N4/Ag2S nanocomposite for selective mercury-ion monitoring in environmental matrices and energy storage applications - Abishek Jayapaul; Sanjay Ballur Prasanna; Lu-Yin Lin; Rajalakshmi Sakthivel; Yu-Chien Lin; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

Establishment of a cobia (Rachycentron canadum) gill cell line: a valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2025)

Uncovering AphBvp-mediated regulation of PirAvp/PirBvp toxins and biofilm formation in AHPND causing Vibrio parahaemolyticus - Michael Eniola Ayenero; Ramya Kumar; Han-Ching Wang; Phuoc Thien Le; Yu-Hsuan Chen; Chu Fang Lo; Shin-Jen Lin; Hao-Ching Wang (Fish & Shellfish Immunology, 2025)

Mitochondrial pyruvate carrier proteins mediate host-pathogen interactions during WSSV infection in shrimp - Yu-Chen Lin; Saengchan Senapin; Pakkakul Sangsuriya; Han-Ching Wang (Fish & Shellfish Immunology, 2025)

Nanoengineered scheelite-structured SrWO4 decorated on MXene sheets: A novel platform for electrochemical sensing of the anti-cancer drug nilutamide with DFT insights - Akash Ashokrao Jagtap; Vaibhav Kanke; Rajalakshmi Sakthivel; Amar S. Katkar; Lu-Yin Lin; Yu-Chien Lin; Xinke Liu; Cihun-Siyong Gong; Ching-Wei Tung; Ren-Jei Chung (Environmental Research, 2025)

Alkylammonium ligands-driven perovskite lattice engineering for white perovskite nanocrystals single emitters - Jean-Sébastien Bénas; Zhen-Li Yan; Wei-Cheng Chen; Chu-Chen Chueh; Jing-Yan Wu; Wei-Wen Chen; Fang-Cheng Liang; Erdi Akman; Yu-Jung Lu; Yen-Yu Wang; Ja-Hon Lin; Ye Zhou; et al. (Chemical Engineering Journal, 2025)

Real-world emissions and total output from fishing vessels in Taiwan - Po-Yen Chien; Chia-Hsiang Lai; Wu-Xing Chen; Chia-Hung Chen; Chia C. Wang; Amila Kasun Abeysinghe; Yi-Ching Lin; Tsai-Jung Yen; Hsiang-Ying Wu; Yu-Lun Tseng; Pei-Shih Chen; Yen-Ping Peng (Transportation Research Part D: Transport and Environment, 2025)

The influence of trees shade level on human thermal comfort and the development of applied assessment tools - Yu-Ying Wei; Ching-Yin Cheng; Tzu-Ping Lin (Landscape and Urban Planning, 2025)

Anaerobic Fe(II) bio-oxidation by Cyanidiophyceae to enhance As(III) removal: A novel and efficient biological material toward resilient remediation - Nhu Anh Thi Than; Liang Ching Hsu; Yu-Hsien Chen; Kamonchanok Huangmee; Chun-Chieh Wang; Heng Yi Teah; Yu-Min Tzou; Yen-Lin Cho; Yu-Ting Liu (Chemical Engineering Journal, 2025)

Anti-cancer effect of Willughbeia edulis Roxb. Stem extract in hepatocellular carcinoma cells through triggering apoptosis and G2/M cell cycle arrest - Thi Tuyet Nhung Nguyen; Yu-Chi Lin; Ching-Kuo Lee; Jing-Jy Cheng (Phytochemistry Letters, 2025)

Discovery of a new 1-monoglyceride from Streptomyces albogriseolus JM128 symbiotic with Lendenfeldia sponge - Yun-Ting Zeng; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; You-Ying Chen; Li-Guo Zheng; Chih-Yin Huang; Hsi-Wen Sun; Ping-Jyun Sung (Phytochemistry Letters, 2025)

High-sensitivity Ara h1 detection with a praseodymium niobate-carbon nanofiber immunosensor - Evangeline Jafneel Nixon; Rajalakshmi Sakthivel; Yu-Chien Lin; Hsiao-Wei Wen; Ching-Wei Tung; Ren-Jei Chung (Food Chemistry, 2025)

Exploring PFRs, ROS, PAHs, nitro-PAHs, and health risks of the nonthermal plasma intervention size-segregated smoldering incense and mosquito coils aerosols - Yu-Chieh Wang; Chia C. Wang; Chon-Lin Lee; Wei-Min Ching (Environmental Pollution, 2025)

Upcycling waste PET into benzoxazines with simultaneously low curing temperatures and high thermal stability - Dula Daksa Ejeta; Meng-Xuan Li; Yu-Kuan Hsu; Muhammad Javed Iqbal; Ching-Hsuan Lin (Chemical Engineering Journal, 2025)

A novel approach for quantifying therapeutic monoclonal antibodies in blood through liquid chromatography–tandem mass spectrometry - Tsun-Hao Chi; Chiao Lo; Shin-Yi Lin; Yi-Hsin Liang; Wen-Chi Chang; Chia-Yu Yeh; Huai-Hsuan Chiu; Ching-Hua Kuo (Analytica Chimica Acta, 2025)

Unveiling Unusual Ecofunctional Traits of Endozoicomonas Species Through Comprehensive Comparative Genomics - Sim Lin Lim; Ching‐Hsiang Chin; Yu‐Jing Chiou; Ming‐Tsung Hsu; Pei‐Wen Chiang; Hsing‐Ju Chen; Yung‐Chi Tu; Wen‐Shyong Tzou; Sen‐Lin Tang (Environmental Microbiology, 2025)
Endozoicomonas is an omnipresent marine bacterial genus, associated with various marine organisms, that contributes to host health, nutrient cycling and disease resistance. Nonetheless, its genomic features remain poorly characterised due to a paucity of high‐quality genomes. In this study, we sequenced 5 novel Endozoicomonas strains and re‐sequenced 1 known strain to improve genomic resolution. By integrating these 6 high‐quality genomes with 31 qualified published genomes, our pan‐genomic analysis revealed variation in genetic traits among clades. Notably, Endozoicomonas lacks quorum‐sensing capabilities, suggesting resistance to quorum quenching mechanisms. It also lacks the capacity to synthesise and transport vitamin B12, indicating that it does not supply this nutrient to holobionts. Remarkably, Endozoicomonas genomes encode 92 identified giant proteins (15–65 kbp). These proteins cluster into three major groups associated with antimicrobial peptide synthesis, exotoxin production and cell adhesion. Additionally, we found that Endozoicomonas has acquired prophages from diverse sources via infection or other types of gene transfer. Notably, CRISPR‐Cas sequences suggest evolutionary trajectories independent of both prophage acquisition and phylogenetic lineage, implying potential geographic influences or environmental pressures. This study provides new insights into the genomic diversity of Endozoicomonas and its genetic adaptations to diverse hosts.

Impact of organic biomass waste composition on anaerobic acid fermentation - Chun-Ching Lu; Yu-Pei Lin; Fang-Yu Hwu (Biomass and Bioenergy, 2025)

Causes, emission characteristics, and health risks of persistent free radicals and reactive oxygen species in PM2.5 produced by smoldering incense - Yu-Chieh Wang; Bo-Yu Chen; Yen-Hsien Li; Tzu-Hsien Tseng; Chon-Lin Lee; Wei-Min Ching (Atmospheric Pollution Research, 2025)

Adaptive fluoride removal across concentration scales: Potential roles of microbial and acicular gypsum interactions in nitrogen and phosphate cycling - Ying-Liang Yu; Wei-Han Lin; Rao Y. Surampalli; Ssu-Ching Chen; Chih-Ming Kao (Journal of Hazardous Materials, 2025)

Development and Evaluation of a Dual-Mode Cold Atmospheric Plasma System for Stage-Specific Wound Healing Applications - Ching-Yuan Lin; Dong-Jin Li; Yu-Shen Chen; Chia-Wei Hsu; Mohd Yaqub Khan; Ming-Chen Wang (Journal of Medical and Biological Engineering, 2025)

Enhanced Hair Growth Through Transdermal Delivery of Bacopa Monnieri Extract Using a Needle-Free Supersonic Atomizer - Yu-Chiuan Wu; Yi-Ping Lin; Ching-Yi Chang; Hsia-Ying Cheng; Tien-Huei Chu; Chien-Chih Chen; Shyh-Ming Kuo (Journal of Medical and Biological Engineering, 2025)

Microplastic-induced hypertension in rats: A two-hit model exploring oxidative stress and gut microbiota - Yu-Chun Cheng; Wei-Ling Chen; Hong-Ren Yu; Ching-Yi Tsai; Jiunn-Ming Sheen; Mao-Meng Tiao; Chien-Ning Hsu; You-Lin Tain (NanoImpact, 2025)

Response and recovery times of vegetation productivity under drought stress: Dominant factors and relationships - Chengyun Wang; Jie Chen; Sung-Ching Lee; Lihua Xiong; Tianhua Su; Qian Lin; Chong-Yu Xu (Journal of Hydrology, 2025)

Synergistic integration of dual Z-scheme Gd2Sn2O7/Ag3PO4/SnS2 heterojunction for accelerated visible-light photodegradation of sulfasalazine: Insights into DFT, toxicity, and antibacterial study - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Susaritha Ramanathan; Sandeep Shadakshari; Kumara Swamy Ningappa; Yu-Chien Lin; Xinke Liu; Ching-Wei Tung; Ren-Jei Chung (Journal of Water Process Engineering, 2025)

Bifunctional approach for electrochemical detection and catalytic degradation of Rhodamine B in environmental samples using a NiFe2O4@C/PPy catalyst: Kinetic and thermodynamic insights - Mosas Vinsy Arul Thomas; Sanjay Ballur Prasanna; Akash Ashokrao Jagtap; Gagankumar Sakleshpur Kumar; Yu-Chien Lin; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2025)

3D printed microtissue cassettes enabling high throughput proton radiobiological assays - Chih-Tsung Yang; I-Chun Cho; Ching-Fang Yu; Edward Cheah; Tesi Liu; Yi-Ping Lin; Sing-Yu Hu; Jyun-Wei Jheng; Ivan Kempson; Tsi-Chian Chao; Sen-Hao Lee; Eva Bezak; et al. (Analytica Chimica Acta, 2025)

Pixel array-based urine biosensor for detection of trimethylamine N-oxide and glucose for early detection of diabetic kidney disease - Mei-Ching Yu; Chi-Jen Lo; Wei-Cheng Lin; Wei-Lun Yen; Yun-Yu Hsieh; Bing-Hong Chen; Fu-Sung Lo (Analytica Chimica Acta, 2025)

Vision transformer-based stratification of pre/diabetic and pre/hypertensive patients from retinal photographs for 3PM applications - Krithi Pushpanathan; Yang Bai; Xiaofeng Lei; Jocelyn Hui Lin Goh; Can Can Xue; Samantha Min Er Yew; Miaoli Chee; Ten Cheer Quek; Qingsheng Peng; Zhi Da Soh; Marco Chak Yan Yu; Jun Zhou; et al. (EPMA Journal, 2025)
Objective Diabetes and hypertension pose significant health risks, especially when poorly managed. Retinal evaluation though fundus photography can provide non-invasive assessment of these diseases, yet prior studies focused on disease presence, overlooking control statuses. This study evaluated vision transformer (ViT)-based models for assessing the presence and control statuses of diabetes and hypertension from retinal images. Methods ViT-based models with ResNet-50 for patch projection were trained on images from the UK Biobank ( n = 113,713) and Singapore Epidemiology of Eye Diseases study ( n = 17,783), and externally validated on the Singapore Prospective Study Programme ( n = 7,793) and the Beijing Eye Study ( n = 6064). Model performance was evaluated using the area under the receiver operating characteristic curve (AUROC) for multiple tasks: detecting disease, identifying poorly controlled and well-controlled cases, distinguishing between poorly and well-controlled cases, and detecting pre-diabetes or pre-hypertension. Results The models demonstrated strong performance in detecting disease presence, with AUROC values of 0.820 for diabetes and 0.781 for hypertension in internal testing. External validation showed AUROCs ranging from 0.635 to 0.755 for diabetes, and 0.727 to 0.832 for hypertension. For identifying poorly controlled cases, the performance remained high with AUROCs of 0.871 (internal) and 0.655–0.851 (external) for diabetes, and 0.853 (internal) and 0.792–0.915 (external) for hypertension. Detection of well-controlled cases also yielded promising results for diabetes (0.802 [internal]; 0.675–0.838 [external]), and hypertension (0.740 [internal] and 0.675–0.807 [external]). In distinguishing between poorly and well-controlled disease, AUROCs were more modest with 0.630 (internal) and 0.512–0.547 (external) for diabetes, and 0.651 (internal) and 0.639–0.683 (external) for hypertension. For pre-disease detection, the models achieved AUROCs of 0.746 (internal) and 0.523–0.590 (external) for pre-diabetes, and 0.669 (internal) and 0.645–0.679 (external) for pre-hypertension. Conclusion ViT-based models show promise in classifying the presence and control statuses of diabetes and hypertension from retinal images. These findings support the potential of retinal imaging as a tool in primary care for opportunistic detection of diabetes and hypertension, risk stratification, and individualised treatment planning. Further validation in diverse clinical settings is warranted to confirm practical utility.

BTEX exposure and metabolite levels in Taiwan schoolchildren near petrochemical areas - Wei-shan Chin; Ching-chun Huang; Yu-cheng Chen; Jing-fang Hsu; Chih-Da Wu; Pinpin Lin; Pau-chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

ONC201 exerts oncogenic effects beyond its mitochondria-disturbing role in neuroblastoma subsets - Jyun-Hong Jiang; Yu-Han Lin; Pei-Lin Liao; Ting-Ya Chen; Hui-Ching Chuang; Chao-Cheng Huang; Wen-Ming Hsu; Jiin-Haur Chuang; Wei-Shiung Lian (Journal of Molecular Medicine, 2025)
Neuroblastoma (NB) is a formidable challenge in pediatric oncology due to its intricate molecular landscape, necessitating multifaceted therapeutic approaches. ONC201 is an imipridone antibiotic compound with a promising drug candidate leveraging its potent anticancer properties against the mitochondrial proteases ClpP and ClpX. Despite demonstrating early clinical promise, particularly in MYCN -amplified NB, its efficacy in non- MYCN -amplified NB remains a subject worthy of investigation. In this study, we extended the coverage of ONC201 to treat non- MYCN -amplified NB, and our data implicated ONC201’s inability to reduce tumor growth in animal models harboring SK-N-AS or SK-N-FI cell lines. Interestingly, ONC201 induced the expression of oncogenic markers c-Myc and LGR5 while downregulating the tumor suppressor ATRX. While it fails to attenuate tumor neovascularization in non- MYCN -amplified NB xenografts, its effectiveness differs from that of its MYCN-amplified counterpart. Rho zero (ρ0)-SK-N-AS cells treated with ONC201 showed comparable observed trends in parental SK-N-AS cells, including LGR5 upregulation and ATRX downregulation, suggesting that ONC201’s multifaceted actions extend beyond mitochondrial targets. Our elucidation highlights the need to discern molecular signatures when deploying ONC201 monotherapy against NB, which lacks MYCN- amplification.

Coral incorporating microplastics leads to a health-risking immunometabolic shift - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li (Chemosphere, 2025)

Knockout of dead end 1 by CRISPR/Cas9 leads to loss of germ cells and male-biased sex development in freshwater angelfish (Pterophyllum scalare) - Wai-Kwan Chu; Shih-Chin Huang; Ching-Fong Chang; Yu-Ho Lin; Jen-Leih Wu; Hong-Yi Gong (Aquaculture, 2025)

Surveillance and genetic diversity of bovine viral diarrhea virus in dairy herds across Taiwan - Fong-Yuan Lin; Hau-You Tzeng; Ching-Yu Tseng; Ruei-Sheng Tsai; Mami Oba; Tetsuya Mizutani; Yumiko Yamada; Hue-Ying Chiou; Shih-Te Chuang; Wei-Li Hsu (The Veterinary Journal, 2025)

Junceellolide Q, a new polyacetoxybriarane from the delicate sea whip octocoral Junceella fragilis - Yih-Gang Goan; Mingzi M. Zhang; Lun Kelvin Tsou; Zhi-Hong Wen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yu-Jen Wu; Jih-Jung Chen; Hai Nhat Do; Pei-Luen Jiang; Ping-Jyun Sung (Phytochemistry Letters, 2025)

Displacement evolution of failure and non-failure sliding rock slopes - Hsien-Li Kuo; Guan-Wei Lin; Ting-Yu Lin; Che-Hsin Liu; Chung-Ray Chu; Chih-Hsin Chang; Ching-Weei Lin; Hongey Chen (Landslides, 2025)

Validation of Automated Standardization Performance for ECDaim Software Developed Using a Taiwan-Specific Database - Yu-Ching Ni; Hui-Chieh Yang; Ing-Tsung Hsiao; Fan-Pin Tseng; Chia-Yu Lin; Wen-Bin Lin; Zong-Jhe Lyu (Journal of Medical and Biological Engineering, 2025)

Kirenol ameliorates endotoxin-induced acute lung injury by inhibiting the ERK and JNK phosphorylation–mediated NFκB pathway in mice - Frank Cheau-Feng Lin; Shih-Pin Chen; Sheng-Chien Lin; Ching-Chi Tseng; Stella Chin-Shaw Tsai; Yu-Hsiang Kuan (Inflammopharmacology, 2025)

Artificial digestion represents the worst-case scenario for studying nanoplastic fate in gastrointestinal tract - Giselle Lee; Ya-Jhu Jhang; Yu-Tung Jhang; Yen-Chen Chang; Hui-Wen Chang; Chun-Yu Chuang; Yung-Kun Chuang; Ching-Wei Lin; I-Lun Hsiao (Journal of Hazardous Materials, 2025)

Proximity to petrochemical industry and risk of childhood asthma occurrence - Shih-Chun Pan; Wei-Shan Chin; Ching-Chun Huang; Yu-Cheng Chen; Chih-Da Wu; Chin-Yu Hsu; Pinpin Lin; Pau-Chung Chen; Yue Leon Guo (International Journal of Hygiene and Environmental Health, 2025)

Safety evaluation of Limosilactobacillus fermentum PS150 for use as a commercial psychobiotic - Li-Hao Cheng; Chien-Chen Wu; Chin-Lin Huang; Yu-Hsuan Wei; Pei-Jun Wen; Shih-Hau Chiu; Chien-Chi Chen; Ching-Ting Lin; Po-Lin Liao (Food and Chemical Toxicology, 2025)

ZFP36L1 and ZFP36L2 reduce cyclin D1 expression by decreasing expression of E2F1 and long 3’UTR isoform of CCND1 transcripts - Tze-Sian Chan; Kun-Lin Lee; Ching-Sheng Hung; Hsin-Pei Chiang; Chia-Chen Chung; Yu-Chih Liang (Molecular and Cellular Biochemistry, 2025)

Correction: CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2025)

Ambient stable ZnBr2-assisted lead-free perovskite for enhanced piezoelectricity of polyvinylidene fluoride in versatile piezo-phototronic applications - Manikandan Venkatesan; Wei-Chun Lin; Wei-Cheng Chen; Jayashree Chandrasekar; Yu-Hang Huang; Kai-Wei Lin; Zih-Syuan Syu; Ja-Hon Lin; Wei-Hung Chiang; Wei-Ren Liu; Ye Zhou; Chi-Ching Kuo (Chemical Engineering Journal, 2025)

Highly active Cu-embedded in magnetic carbon nanofibers for the reduction of 4-nitrophenol - Ching-Shiun Chen; Tse-Ching Chen; Kai-Lin Chiu; Cheng-Rong Hsing; Li-Yu Wang; Chia-Min Yang; Chih-Wen Pao; Chi-Liang Chen (Chemical Engineering Journal, 2025)

Digital transformation of mental health therapy by integrating digitalized cognitive behavioral therapy and eye movement desensitization and reprocessing - Ju-Yu Wu; Ying-Ying Tsai; Yu-Jie Chen; Fan-Chi Hsiao; Ching-Han Hsu; Yen-Feng Lin; Lun-De Liao (Medical & Biological Engineering & Computing, 2025)

Using Gaussian Mixture Model Clustering for the Automated Segmentation of Cerebral Arteriovenous Malformations in Magnetic Resonance Images - Ting-Yu Lin; Cheng‑Chia Lee; Yu-Wei Chen; Hsiu-Mei Wu; Ching-Jen Chen; Huai-Che Yang; Syu-Jyun Peng (Journal of Medical and Biological Engineering, 2025)

Analysis of serotype distribution and characteristics of nonhemolytic and nonpigmented strains among group B Streptococcus isolates in a southern Taiwan local hospital - Hui-Fang Cheng; Zhe-Yu Kuo; Ching-Chiang Lin; Ho-Feng Chen; Horng-Ren Lo; Huey-Wen Shyu; Yi-Fen Wang (European Journal of Clinical Microbiology & Infectious Diseases, 2025)

Enhanced nano-LC-MS for analyzing dansylated oral cancer tissue metabolome dissolved in solvents with high elution strength - Ya-Ju Hsieh; Cheng-Yu Hung; Yi-Ting Chen; Yu-Tsun Lin; Kai-Ping Chang; Wei-Fan Chiang; Chih-Yen Chien; Chih-Ching Wu; Liang Li; Jau-Song Yu; Kun-Yi Chien (Analytica Chimica Acta, 2025)

Dual functionality of carbazole-based phosphonic acid molecular additives realizes efficient hole transport layer-free perovskite light-emitting diodes - Yin-Ti Lai; Chiung-Han Chen; Ming-Hsuan Yu; Hsing-Yu Kuo; I-Chih Ni; Bi-Hsuan Lin; Hobeom Kim; Chi-Ching Kuo; Yu-Jung Lu; Chu-Chen Chueh (Chemical Engineering Journal, 2025)

Deep learning in the advanced core sample porosity determination with XCT image - Hung-Yu Wu; Ching-Li Kuo; Chen-Yi Lin; Wei-Ta Chu (Earth Science Informatics, 2025)

Nanoplastics indirectly compromise lettuce growth in hydroponic systems via microbial extracellular vesicles derived from Curvibacter fontanus - Bao-Hong Lee; Yi-Ching Lin; Yu-Juan Zheng; Tang-Long Shen; Ting-Yu Cheng; Chih-Chia Huang; Wei-Hsuan Hsu (Journal of Hazardous Materials, 2024)

Bio-inspired sustainable electrospun quantum nanostructures for high quality factor enabled face masks and self-powered intelligent theranostics - Loganathan Veeramuthu; Ren-Jie Weng; Wei-Hung Chiang; Archana Pandiyan; Fu-Jie Liu; Fang-Cheng Liang; G. Ranjith Kumar; Hua-Yi Hsu; Yu-Ci Chen; Wen-Yinn Lin; Yao-Chun Tang; Wan-Rong Lin; et al. (Chemical Engineering Journal, 2024)

The Association Among Urinary Di-(2-ethylhexyl) Phthalate Metabolites, Serum Lipid Profiles, and Serum Apoptotic Microparticles in a Young Taiwanese Population - Chien-Yu Lin; Sandy Huey-Jen Hsu; Ching-Way Chen; Chikang Wang; Fung-Chang Sung; Ta-Chen Su (Exposure and Health, 2024)

Analysis of chemosensitivity of tumor spheroids exposed to two-dimensional gradient of combination drugs in a hydrogel-based diffusion microfluidic platform - Kin Fong Lei; Yu-Ting Lin; Sai Kiran Reddy Boreddy; Ping-Ching Pai (Analytica Chimica Acta, 2024)

Comprehensive evaluation of the nephrotoxicity of carbon quantum dots: Effects of the surface charge - Pei-Luen Jiang; Yan-Yu Hong; Lingyan Yang; Han-Jia Lin; Chih-Ching Huang; Yan-Hua Chen; Chia-Hua Lin; Yi-Chun Chen (Chemosphere, 2024)

Development of fermented Atemoya (Annona cherimola × Annona squamosa)-Amazake increased intestinal next-generation probiotics - Yeu-Ching Shi; She-Ching Wu; Yi-Ching Lin; Yu-Juan Zheng; Cheng-Hao Huang; Bao-Hong Lee (Food Chemistry, 2024)

Rational design of stable Cu and AuCu nanoparticles for investigations of size-enhanced SERS applications - Kuan-Wen Liu; Pei-Yu Sie; Jing-Yin Huang; Hsi-Ying Chen; Yi-Lun Chen; Yu-Ching Lin; Mei-Yi Liao (Analytica Chimica Acta, 2024)

Health risks of environmentally persistent free radicals in atmospheric particulate matter during the spring festival travel season in Tainan, Taiwan - Yu-Chieh Wang; Wei-Min Ching; Chon-Lin Lee (Environmental Science and Pollution Research, 2024)

Development of Quantitative Norms for Normal Lung Uptake Based on Three-Dimensional Gallium-67 Single Photon Emission Computed Tomography/Computed Tomography - Tzyy-Ling Chuang; Wei-Lin Li; Yu-Ching Hs; Jyh-Cheng Chen; Yuh-Feng Wang (Journal of Medical and Biological Engineering, 2024)
Purpose Gallium-67 (Ga-67) lung scans assess alveolitis and interstitial lung disease, with Ga-67 accumulation correlating with inflammation intensity as seen in lung biopsy sections. Both semi-quantitative and quantitative methods have been used, with the latter providing an inflammatory activity index linked to lung lavage and histopathological scores. However, differing reference points result in varying outcomes. This study aimed to establish standard Ga-67 index parameters using semi-quantitative analysis and a linear regression model based on planar and SPECT/CT images. Methods Twenty subjects without lung disease received a 5–6 mCi Ga-67 injection via the ankle. Both planar and SPECT/CT images were analyzed, with semi-quantitative values assessed using GraphPad Prism 9.5.1. Results Compared to planar images, SPECT/CT acquisitions for the lung-to-arm uptake ratio proved the most reliable indicator for assessing lung inflammation. Increased lung Ga-67 uptake was defined as greater than 2 standard deviations from the average Ga-67 uptake for healthy subjects. The normal range was 0.065 ± 0.049 for the right side and 0.076 ± 0.070 for the left side. Conclusion Lung-to-arm ratios in SPECT/CT images are more accurate than those in planar images. This method should be adopted as a standard clinical practice, providing more reliable diagnostic information and improving patient management. Future studies should compare patients without lung disease to those with lung disease to determine the diagnostic benefit of these norms.

The impact of flooding from the Minjiang River on the succession of harmful algal blooms (HABs) caused by diatoms in China's offshore waters - Yun-Chi Lin; Ya-Han Nien; Kuo-Ping Chiang; Chien-Pang Chin; Wei-Ting Chen; Gwo-Ching Gong; Wen-Chen Chou; Chi-Yu Shih; Kuo-Shu Chen (Marine Pollution Bulletin, 2024)

Organic light-emitting diode therapy promotes longevity through the upregulation of SIRT1 in senescence-accelerated mouse prone 8 mice - Yue-Hua Deng; Chi-Sheng Chiou; Ching-Yu Tsai; Abhinay Kumar Singh; Edlin Anahi Pelaze Achtmann; Bou-Yue Peng; Tommy Yet-Min Lin; Hsin-Chung Cheng; Pao-Chang Chiang; Win-Ping Deng (Journal of Photochemistry and Photobiology B: Biology, 2024)

Design of a pebbles-like erbium stannate integrated with graphene nanoribbons for the anti-cancer drug nilutamide detection in water and biological samples - Abishek Jayapaul; Rajesh Kumar Panda; Sayee Kannan Ramaraj; Lu-Yin Lin; Yeh-Fang Duann; Yu-Chien Lin; Yu-Chun Lu; Wai-Ching Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Journal of Environmental Chemical Engineering, 2024)

Policies for reducing the greenhouse gas emissions generated by the road transportation sector in Taiwan - Ching-Chih Chang; Kuei-Chao Chang; Yu-Lien Lin (Energy Policy, 2024)

Accumulation and bio-oxidation of arsenite mediated by thermoacidophilic Cyanidiales: innate potential biomaterials toward arsenic remediation - Yen-Lin Cho; Yu-Min Tzou; Afifah Assakinah; Nhu Anh Thi Than; Hwan Su Yoon; Seung In Park; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Pei-Yu Huang; Shao-Lun Liu; Yu-Ting Liu (Bioresource Technology, 2024)

Predicting ischemic stroke patients’ prognosis changes using machine learning in a nationwide stroke registry - Ching-Heng Lin; Yi-An Chen; Jiann-Shing Jeng; Yu Sun; Cheng-Yu Wei; Po-Yen Yeh; Wei-Lun Chang; Yang C. Fann; Kai-Cheng Hsu; Jiunn-Tay Lee (Medical & Biological Engineering & Computing, 2024)
Accurately predicting the prognosis of ischemic stroke patients after discharge is crucial for physicians to plan for long-term health care. Although previous studies have demonstrated that machine learning (ML) shows reasonably accurate stroke outcome predictions with limited datasets, to identify specific clinical features associated with prognosis changes after stroke that could aid physicians and patients in devising improved recovery care plans have been challenging. This study aimed to overcome these gaps by utilizing a large national stroke registry database to assess various prediction models that estimate how patients’ prognosis changes over time with associated clinical factors. To properly evaluate the best predictive approaches currently available and avoid prejudice, this study employed three different prognosis prediction models including a statistical logistic regression model, commonly used clinical-based scores, and a latest high-performance ML-based XGBoost model. The study revealed that the XGBoost model outperformed other two traditional models, achieving an AUROC of 0.929 in predicting the prognosis changes of stroke patients followed for 3 months. In addition, the XGBoost model maintained remarkably high precision even when using only selected 20 most relevant clinical features compared to full clinical datasets used in the study. These selected features closely correlated with significant changes in clinical outcomes for stroke patients and showed to be effective for predicting prognosis changes after discharge, allowing physicians to make optimal decisions regarding their patients’ recovery. Graphical Abstract

CCL4 contributes to aging related angiogenic insufficiency through activating oxidative stress and endothelial inflammation - Ting-Ting Chang; Liang-Yu Lin; Ching Chen; Jaw-Wen Chen (Angiogenesis, 2024)
Aging is a natural process associated with chronic inflammation in the development of vascular dysfunction. We hypothesized that chemokine C-C motif ligands 4 (CCL4) might play a vital role in aging-related vascular dysfunction. Circulating CCL4 was up-regulated in elderly subjects and in aged animals. CCL4 inhibition reduced generation of reactive oxygen species (ROS), attenuated inflammation, and restored cell functions in endothelial progenitor cells from elderly subjects and in aged human aortic endothelial cells. CCL4 promoted cell aging, with impaired cell functioning, by activating ROS production and inflammation. CCL4 knockout mice and therapeutic administration of anti-CCL4 neutralizing antibodies exhibited vascular and dermal anti-aging effects, with improved wound healing, via the down-regulation of inflammatory proteins and the activation of angiogenic proteins. Altogether, our findings suggested that CCL4 may contribute to aging-related vascular dysfunction via activating oxidative stress and endothelial inflammation. CCL4 may be a potential therapeutic target for vascular protections during aging.

Kaguacidine A: a novel spirohydantoin-containing cucurbitane glycoside from vines of Momordica charantia L. - Hung-Tse Huang; I-Wen Lo; Yu-Chi Lin; Liao Geng-You; Yun-Sheng Lin; Li-Jie Zhang; Tsung-Lin Li; Chia-Ching Liaw; Yao-Haur Kuo (Natural Product Research, 2024)

Efficiency of PGK1 proteins delivered to the brain via a liposomal system through intranasal route administration for the treatment of spinocerebellar ataxia type 3 - Yu-Shuan Chen; Zhen-Xiang Hong; Yi-Tung Lin; En-CI Tsao; Pei-Yu Chen; Ching-Ann Liu; Horng-Jyh Harn; Tzyy-Wen Chiou; Shinn-Zong Lin (Drug Delivery and Translational Research, 2024)

Assessment of PM2.5-associated mortality burden among the elderly: Insights into demographic, socio-economic, and geographic factors - Ayushi Sharma; Hsi-yu Hsiao; Jia-Yi Liu; Shih-Chun Candice Lung; Huey-Jen Su; Ching-Fen Shen; Nai-Tzu Chen; Pei-Chih Wu; Cheng-Yu Lin; Sheng-Fu Liang; Tain-Junn Cheng; Ta-Chien Chan; et al. (Air Quality, Atmosphere & Health, 2024)

A Ce2MgMoO6 double perovskite decorated on a functionalized carbon nanofiber nanocomposite for quantification of ciprofloxacin in milk and honey samples: Density functional theory interpretation - Akash Ashokrao Jagtap; Sanjay Ballur Prasanna; Gagankumar Sakaleshpur Kumar; Yu-Chien Lin; Udesh Dhawan; Yu-Chun Lu; Rajalakshmi Sakthivel; Ching-Wei Tung; Ren-Jei Chung (Chemosphere, 2024)

Isolation of 24-homoscalarane sesterterpenoids from a sponge of the genus Lendenfeldia - Li-Guo Zheng; You-Yan Chen; Chia-Ching Liaw; Yu-Chi Lin; Su-Ying Chien; Yi-Hao Lo; Yu-Chi Tsai; Hao-Chun Hu; You-Ying Chen; Tsong-Long Hwang; Tzu-Ming Ou; Ping-Jyun Sung (Phytochemistry Letters, 2024)

Thiol-functionalized black carbon as effective and economical materials for Cr(VI) removal: Simultaneous sorption and reduction - Kamonchanok Huangmee; Liang-Ching Hsu; Yu-Min Tzou; Yen-Lin Cho; Chih-Hao Liao; Heng Yi Teah; Yu-Ting Liu (Journal of Environmental Management, 2024)

Efficiencies of filtration sampling and extraction for recovery of viable Staphylococcus aureus bioaerosols - Ching-Wen Chang; Yen-Ni Lin; Sheng-Hsiu Huang; Yu-Ju Horng (Journal of Aerosol Science, 2024)

Advancing Li3VO4 as a high-performance anode material for use in lithium-ion batteries and lithium-ion capacitors - Yu-Sheng Hsiao; Jen-Hsien Huang; Lin-Yang Weng; Ta-Hung Cheng; Han-Hsin Chiang; Cheng-Zhang Lu; Huei-Chu Weng; Lars Thomsen; Bruce Cowie; Wei Kong Pang; Yu-Ching Huang (Chemical Engineering Journal, 2024)

Examining arterial pulsation to identify and risk-stratify heart failure subjects with deep neural network - Chieh-Chun Huang; Shih-Hsien Sung; Wei-Ting Wang; Yin-Yuan Su; Chi-Jung Huang; Tzu-Yu Chu; Shao-Yuan Chuang; Chern-En Chiang; Chen-Huan Chen; Chen-Ching Lin; Hao-Min Cheng (Physical and Engineering Sciences in Medicine, 2024)
Hemodynamic parameters derived from pulse wave analysis have been shown to predict long-term outcomes in patients with heart failure (HF). Here we aimed to develop a deep-learning based algorithm that incorporates pressure waveforms for the identification and risk stratification of patients with HF. The first study, with a case–control study design to address data imbalance issue, included 431 subjects with HF exhibiting typical symptoms and 1545 control participants with no history of HF (non-HF). Carotid pressure waveforms were obtained from all the participants using applanation tonometry. The HF score, representing the probability of HF, was derived from a one-dimensional deep neural network (DNN) model trained with characteristics of the normalized carotid pressure waveform. In the second study of HF patients, we constructed a Cox regression model with 83 candidate clinical variables along with the HF score to predict the risk of all-cause mortality along with rehospitalization. To identify subjects using the HF score, the sensitivity, specificity, accuracy, F1 score, and area under receiver operating characteristic curve were 0.867, 0.851, 0.874, 0.878, and 0.93, respectively, from the hold-out cross-validation of the DNN, which was better than other machine learning models, including logistic regression, support vector machine, and random forest. With a median follow-up of 5.8 years, the multivariable Cox model using the HF score and other clinical variables outperformed the other HF risk prediction models with concordance index of 0.71, in which only the HF score and five clinical variables were independent significant predictors (p < 0.05), including age, history of percutaneous coronary intervention, concentration of sodium in the emergency room, N -terminal pro-brain natriuretic peptide, and hemoglobin. Our study demonstrated the diagnostic and prognostic utility of arterial waveforms in subjects with HF using a DNN model. Pulse wave contains valuable information that can benefit the clinical care of patients with HF.

Correction: Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)

Establishment of a cobia (Rachycentron canadum) gill cell line: A valuable tool for immune response studies - Thi Hang Ho; Hoang Trieu Quan Tran; Chun-Hung Liu; Meng-Chou Lee; Eakapol Wangkahart; Yu-Ching Wu; Yu-Lin Lin; Po-Tsang Lee (Fish & Shellfish Immunology, 2024)

Spontaneous mutations and mutational responses to penicillin treatment in the bacterial pathogen Streptococcus pneumoniae D39 - Wanyue Jiang; Tongtong Lin; Jiao Pan; Caitlyn E. Rivera; Clayton Tincher; Yaohai Wang; Yu Zhang; Xiang Gao; Yan Wang; Ho-Ching T. Tsui; Malcolm E. Winkler; Michael Lynch; et al. (Marine Life Science & Technology, 2024)
Bacteria with functional DNA repair systems are expected to have low mutation rates due to strong natural selection for genomic stability. However, our study of the wild-type Streptococcus pneumoniae D39, a pathogen responsible for many common diseases, revealed a high spontaneous mutation rate of 0.02 per genome per cell division in mutation-accumulation (MA) lines. This rate is orders of magnitude higher than that of other non-mutator bacteria and is characterized by a high mutation bias in the A/T direction. The high mutation rate may have resulted from a reduction in the overall efficiency of selection, conferred by the tiny effective population size in nature. In line with this, S. pneumoniae D39 also exhibited the lowest DNA mismatch-repair (MMR) efficiency among bacteria. Treatment with the antibiotic penicillin did not elevate the mutation rate, as penicillin did not induce DNA damage and S. pneumoniae lacks a stress response pathway. Our findings suggested that the MA results are applicable to within-host scenarios and provide insights into pathogen evolution.

Nucleocytoplasmic shuttling of BEFV M protein-modulated by lamin A/C and chromosome maintenance region 1 through a transcription-, carrier- and energy-dependent pathway - Yu-Kang Chang; Yi-Jyum Lin; Ching-Yuan Cheng; Pei-Chien Tsai; Chi-Young Wang; Brent L. Nielsen; Hung-Jen Liu (Veterinary Microbiology, 2024)

Assessing cardiovascular toxicity in zebrafish embryos exposed to copper nanoparticles - Bu-Yuan Hsiao; Jiun-Lin Horng; Ching-Hua Yu; Wen-Ting Lin; Yu-Han Wang; Li-Yih Lin (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

In-Situ synthesis of NbC Nanoparticle-Decorated Polyimide-Derived graphene for enhanced thermal management - Yu-Sheng Hsiao; Chao-Yuan Lin; Lin-Yang Weng; Chun-Han Hsu; Ta-Hung Cheng; Jen-Hsien Huang; Nian-Jheng Wu; Wei Kong Pang; Shih-Chieh Hsu; Huei Chu Weng; Yu-Ching Huang (Chemical Engineering Journal, 2024)

TALE-based organellar genome editing and gene expression in plants - Jer-Young Lin; Yu-Chang Liu; Yan-Hao Tseng; Ming-Tsair Chan; Ching-Chun Chang (Plant Cell Reports, 2024)

Photo-protection and photo-inhibition during light induction in Barbula indica and Conocephalum conicum under different light gradients - Chung-I. Chen; Kuan-Hung Lin; Meng-Yuan Huang; Kuei-Yu Yao; Chau-Ching Huang; Tzu-Chao Lin; En-Liang Chu; Jia-Dong Yang; Ching-Wen Wang (Photosynthesis Research, 2024)

Shrimp SIRT4 promotes white spot syndrome virus replication - Yu Kent Tan; Brandon Rafael de Jesús Castillo-Corea; Ramya Kumar; Ping-Hung Lai; Shih-Shun Lin; Han-Ching Wang (Fish & Shellfish Immunology, 2024)

Effect of stress on the rehabilitation performance of rats with repetitive mild fluid percussion-induced traumatic brain injuries - Yu-Lin Wang; Chi-Chun Chen; Ching-Ping Chang (Cognitive Neurodynamics, 2024)

Microplastics elicit an immune-agitative state in coral - Chuan-Ho Tang; Ching-Yu Lin; Hsing-Hui Li; Fu-Wen Kuo (Science of The Total Environment, 2024)

2D/2D heterostructure Ni-Fe LDH/black phosphorus nanosheets with AuNP for noxious substance diphenylamine detection in food samples - Sanjay Ballur Prasanna; Yu-Chien Lin; Sayee Kannan Ramaraj; Udesh Dhawan; Xinke Liu; Ching-Wei Tung; Rajalakshmi Sakthivel; Ren-Jei Chung (Food Chemistry, 2024)

Evaluating the toxic mechanism of 1,2-diacetylbenzene in neural cells/tissues: The favorable impact of silibinin - Li-Yu Fay; Jun-Yi Chien; Ching-Feng Weng; Huai-Sheng Kuo; Dann-Ying Liou; Wei-Hao Weng; Chi-Hung Lin; Ya-Tzu Chen; Wen-Hung Huang; Wen-Cheng Huang; May-Jywan Tsai; Henrich Cheng (NeuroToxicology, 2023)

A crosslinked waterborne poly(vinyl acetate) for greenhouse gas fixation with improved elastomeric properties, shape-memory ability, and recyclability - Yen-Chuan Chen; Ying-Chi Huang; Yi-Hua Huang; Ying-Feng Lin; Ho-Ching Huang; Ru-Jong Jeng; Yu-Wei Cheng; Chien-Hsin Wu (Journal of Environmental Chemical Engineering, 2023)

Effectiveness and safety of botulinum neurotoxin for treating dyssynergic defecation: A systematic review and meta-analysis - Ching-Yu Chu; Yu-Chi Su; Pei-Chun Hsieh; Yu-Ching Lin (Toxicon, 2023)

Association between glyphosate exposure and cognitive function, depression, and neurological diseases in a representative sample of US adults: NHANES 2013–2014 analysis - Ching Chung Hsiao; An-Ming Yang; ChiKang Wang; Chien-Yu Lin (Environmental Research, 2023)

Corrigendum to “PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet” [Toxicology and Applied Pharmacology, 470, (2023), 116557] - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

The biocompatibility and hemostatic efficacy of silk fibroin nanofibrils fabricated by Shear-Induced phase separation process - Po-Wen Lu; Yu-Tzu Wu; Liang-Yu Chang; Tzu-Wei Lu; Chonlachat Jaihao; Ching-Shuan Huang; Mo-Fei Murphy Chuang; Chunche Lin; Innie Chen; Agnese Brangule; Aleksej Zarkov; Aivaras Kareiva; et al. (Chemical Engineering Journal, 2023)

Severity of Liver Cirrhosis Evaluated by Digital Subtraction Angiography Using Quantitative Color-Coding Analysis Before Transarterial Embolization - Lung-Hui Giiang; Chang-Hsien Liu; Chih-Yung Yu; Te-Pao Lin; Hsiang-Cheng Chen; Chun-Jung Juan; Yu-Ching Chou (Journal of Medical and Biological Engineering, 2023)

A concise chemoenzymatic total synthesis of neutral Globo-series glycosphingolipids Globo A and Globo B, and Forssman and para-Forssman antigens - Yu-Ching Chiang; Chun-Yen Wu; Pei-Yun Chiang; Avijit K. Adak; Chun-Cheng Lin (Glycoconjugate Journal, 2023)

Exposure to incense burning, biomarkers, and the physical health of temple workers in Taiwan - Su-Er Guo; Pamela A. Ratner; Sung-Chih Tseng; Chieh-Mo Lin; Miao-Ching Chi; Chiang-Wen Lee; Ying-Chun Yu (Environmental Science and Pollution Research, 2023)
Incense burning releases heavy particulate matter (PM) and nitrogen dioxide (NO 2 ), known to have adverse effects on human health. Long-term exposure to PM and NO 2 increases inflammatory cytokine levels and can induce respiratory diseases. This study examined the association between incense burning exposure and the health status, especially inflammatory biomarkers, of temple workers and volunteers in Taiwan. The longitudinal observational study compared adult temple workers and volunteers, with long-term incense burning exposure, to residents from outpatient clinics in the Chiayi area. Forced expiratory volume in 1 s (FEV1) and serum and exhaled breath condensate (EBC) cytokines were assessed. Nonparametric Mann-Whitney U tests were used to compare cytokine levels of the exposure and control groups during the cold and hot weather seasons. FEV1 was significantly more diminished in the exposed group than in the control group during the cold season. Exposure status was associated with greater hot-cold seasonal differences in serum interleukins (IL)-1β (regression coefficient ( B ) = 6.6, 95% confidence interval (CI) = 5.0 to 8.3, p < .001), IL17-A ( B = 2.4, 95% CI = 0.3 to 4.5, p = .03), and plasminogen activator inhibitor [PAI]-1 ( B = 5.4, 95% CI = 1.5 to 9.3, p = .009). After adjusting for confounders, the groups’ serum levels of IL-1β, IL-17A, and PAI-1 significantly differed. EBC cytokines did not show significant differences. Elevated levels of IL-1β, IL17-A, and PAI-1 have been associated with various autoinflammatory syndromes and diseases. Given the cultural significance of incense burning, culturally sensitive interventions, including education, policy development, and program implementation, are crucial to protect individuals’ health, especially temple workers, from the adverse effects of exposure, addressing the manufacture, importation, and sale of incense.

Dynamic total factors’ environmental efficiency in European union countries - Ching-Cheng Lu; Yung-ho Chiu; I-Fang Lin; Tai-Yu Lin (Environment, Development and Sustainability, 2023)

Cleanup of Cr(VI)-polluted groundwater using immobilized bacterial consortia via bioreduction mechanisms - Wei-Han Lin; Chih-Ching Chien; Jiun-Hau Ou; Ying-Liang Yu; Ssu-Ching Chen; Chih-Ming Kao (Journal of Environmental Management, 2023)

Regulating energy gap in Ir-based ionic complexes to generate near-infrared emissions: Application in solid-state light-emitting electrochemical cells - Yan-Ding Lin; Pei-Wan Hsiao; Wun-Yu Chen; Sih-Yu Wu; Wei-Min Zhang; Chin-Wei Lu; Hai-Ching Su (Chemical Engineering Journal, 2023)

New ent -kaurene and germacrene derivatives from Mesona procumbens Hemseley and their biological activity - Jerome G. Ganzon; Chia-Ching Liaw; Yu-Chi Lin; Zhi-Hu Lin; Chang-Hung Wang; Che-Yi Chen; Kuo-Hsiang Chuang; Yao-Haur Kuo (Natural Product Research, 2023)

Estimating arsenic biotransfer factors from feed to chicken: a viable approach to animal feed risk assessment - Ching-Chi Hung; Hsin-Tang Lin; Ching-Yi Chen; Kuan-Yi Chen; Tsung-Yu Lee; Chow-Feng Chiang (Food Additives & Contaminants: Part A, 2023)

PKC-δ-dependent mitochondrial ROS attenuation is involved as 9-OAHSA combats lipoapotosis in rat hepatocytes induced by palmitic acid and in Syrian hamsters induced by high-fat high-cholesterol high-fructose diet - Ching-Hui Loh; Wei-Wen Kuo; Shinn-Zong Lin; Cheng-Yen Shih; Pi-Yu Lin; Jiro Hasegawa Situmorang; Chih-Yang Huang (Toxicology and Applied Pharmacology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Phylogenetic divergence associated with climate oscillations and topology illustrates the dispersal history of Formosan sambar deer (Rusa unicolor swinhoii) in Taiwan - Kuan-Yi Li; Chen Hsiao; Shih-Ching Yen; Chien-Yi Hung; You-Zhu Lin; Sheng-Wun Jheng; Pei-Ju Yu; Mei-Hsiu Hwang; Guo-Jing Weng; Ku-Lin Chen; Shu-Fen Lin; Shih-Wei Chang; et al. (Mammal Research, 2023)
The island of Taiwan represents an ideal context for studying the effects of climatic oscillations and topographic variation on large herbivores due to its varied tropical to sub-tropical climate zones at different elevational ranges. We explored the phylogenetics of Formosan sambar deer ( Rusa unicolor swinhoii ) using the control region of the mitochondrial genome. We detected 18 haplotypes among 454 sequences across the island and grouped them into six regions based on SAMOVA, with 68.78% variance among regions. A Bayesian phylogenetic dendrogram revealed two spatially segregated genetic clades. Neutrality tests and Bayesian skyline plots uncovered different demographic expansion histories for the two clades. We further tested divergence times and chronology to propose potential phylogenetic scenarios, which were examined using approximate Bayesian computation. Finally, we present a credible hypothesis for a glacial refugium in the northern part of the Central Mountain Range. Subsequent secondary contact between the two clades during interglacial periods has led to the extant genetic structure of Formosan sambar deer.

Long-term DEHP/MEHP exposure promotes colorectal cancer stemness associated with glycosylation alterations - Pei-Chun Shih; Hsin-Pao Chen; Ching-Cheng Hsu; Chung-Hsien Lin; Chou-Yuan Ko; Chao-Wen Hsueh; Cheng-Yi Huang; Tian-Huei Chu; Cheng-Chun Wu; Yu-Cheng Ho; Ngoc Uyen Nhi Nguyen; Shih-Chung Huang; et al. (Environmental Pollution, 2023)

Early-onset caloric restriction alleviates ageing-associated steatohepatitis in male mice via restoring mitochondrial homeostasis - Chun-Hsien Chiang; Sin-Jin Li; Yu-Han Lin; Pei-Yu Wang; Pu-Sheng Hsu; Shau-Ping Lin; Ting-Chia Chiang; Ching-Yi Chen (Biogerontology, 2023)

Assessing the ecosystem services provided by conventional and organic farmlands: A better outcome for organic farmlands? - Ching-Hua Hsieh; Hsing-Wei Lin; Wan-Yu Liu (Ecosystem Services, 2023)

Removal and concurrent reduction of Cr(VI) by thermoacidophilic Cyanidiales: a novel extreme biomaterial enlightened for acidic and neutral conditions - Yen-Lin Cho; Yu-Min Tzou; Chun-Chieh Wang; Yao-Chang Lee; Liang-Ching Hsu; Shao-Lun Liu; Afifah Assakinah; Yu-Hsien Chen; Nhu Anh Thi Than; Yu-Ting Liu; Jörg Rinklebe (Journal of Hazardous Materials, 2023)

Clay nanosheets simultaneously intercalated and stabilized by PEGylated chitosan as drug delivery vehicles for cancer chemotherapy - Hsuan-Jung Huang; Shih-Yu Huang; Tzu-Hao Wang; Tzu-Yun Lin; Nan-Ching Huang; Orion Shih; U-Ser Jeng; Che-Yi Chu; Wen-Hsuan Chiang (Carbohydrate Polymers, 2023)

Adopting abundant seawater as green chemical activators for preparing high surface area biochar - TsingHai Wang; Yu-Ching Lin; Ci-Jing Hung; Yasi Liao; Ruo-Xin Xu (Bioresource Technology Reports, 2023)

Two-stage dynamic data envelopment analysis measuring the overall efficiency and productivity changes of industry and agriculture in EU countries - Ching-Cheng Lu; I-Fang Lin; Tai-Yu Lin; Yung-ho Chiu (Journal of Cleaner Production, 2023)

Identification of serum metabolic signatures of environmental-leveled phthalate in the Taiwanese child population using NMR-based metabolomics - Sheng-Han Lee; Zhi-Yi Du; Wei-Chen Tseng; Wan-Yu Lin; Mei-Huei Chen; Ching-Chun Lin; Hao-Jan Liang; Hui-Ju Wen; Yue-Leon Guo; Pau-Chung Chen; Ching-Yu Lin (Environmental Pollution, 2023)

13.2% EQE near-infrared TADF OLED with emission peak at 761 nm - Jing-Wen Tai; Yukun Tang; Kai Zhang; Chen-Zong Yang; Ze-Hui Pan; Yu-Ching Lin; Yu-Wei Shih; Chia-Hsun Chen; Tien-Lung Chiu; Jiun-Haw Lee; Chuan-Kui Wang; Chung-Chih Wu; et al. (Chemical Engineering Journal, 2023)

ZAKβ Alleviates Oxidized Low-density Lipoprotein (ox-LDL)-Induced Apoptosis and B-type Natriuretic Peptide (BNP) Upregulation in Cardiomyoblast - Yueh-Min Lin; Jiro Hasegawa Situmorang; Jia-Zun Guan; Dennis Jine-Yuan Hsieh; Jaw-Ji Yang; Michael Yu-Chih Chen; Ching-Hui Loh; Chia-Hua Kuo; Shang-Yeh Lu; Ying-Ming Liou; Chih-Yang Huang (Cell Biochemistry and Biophysics, 2022)

Correction to: Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Streptococcus vulneris sp. nov., isolated from wound of patient with diabetic foot ulcer (DFU) - Jen-hao Chung; Li-Ting Wang; Yi-Sheng Chen; Yun-Shien Lee; Shih-Ting Lin; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Jui-hsiang Li (Archives of Microbiology, 2022)

Lactobacillus plantarum PS128 Promotes Intestinal Motility, Mucin Production, and Serotonin Signaling in Mice - Chih-Ming Chen; Chien-Chen Wu; Chin-Lin Huang; Min-Yu Chang; Shih-Hsuan Cheng; Ching-Ting Lin; Ying-Chieh Tsai (Probiotics and Antimicrobial Proteins, 2022)
Lactobacillus plantarum PS128 has been reported as a psychobiotic to improve mental health through the gut–brain axis in experimental animal models. To explore its mechanism of action in the gut, this study aimed to analyze the effects of L. plantarum PS128 ingestion on naïve and loperamide (Lop)-induced constipation mice. We found that, in the two mouse models, the weight, number, and water content of feces in the L. plantarum PS128 group were higher than those in the vehicle control group. Histological observation revealed that L. plantarum PS128 increased the level of colonic mucins including the major mucin MUC2. In addition, the charcoal meal test showed that L. plantarum PS128 significantly increased the small intestine transit in naïve mice, but not in the Lop-treated mice. Since intestinal serotonin has been found to modulate motility, we further analyzed the expression of genes related to serotonin signal transduction in the small intestine of naïve mice. The results showed that L. plantarum PS128 significantly altered the expression levels of Tph1 , Chga , Slc6a4 , and Htr4 , but did not affect the expression levels of Tph2 , Htr3a , and Maoa . Furthermore, immunohistochemistry revealed that L. plantarum PS128 significantly increased the number of serotonin-containing intestinal cells in mice. Taken together, our results suggest that L. plantarum PS128 could promote intestinal motility, mucin production, and serotonin signal transduction, leading to a laxative effect in mice.

Exercise Rehabilitation and/or Astragaloside Attenuate Amyloid-beta Pathology by Reversing BDNF/TrkB Signaling Deficits and Mitochondrial Dysfunction - Yu-Lin Wang; Chung-Ching Chio; Shu-Chun Kuo; Chao-Hung Yeh; Jui-Ti Ma; Wen-Pin Liu; Mao-Tsun Lin; Kao-Chang Lin; Ching-Ping Chang (Molecular Neurobiology, 2022)

Anti-inflammatory constituents from Phyllostachys makinoi Hayata - Chia-Ching Liaw; Yu-Chi Lin; Shao-Yu Wu; Jenny Chun-Ling Kuo; Zhi-Hu Lin; Kai-Wei Lin; Huang Hui-Chi; Li-Ming Yang Kuo; Yao-Haur Kuo (Natural Product Research, 2022)

Evaluating the energy, health efficiency, and productivity in OECD - Ching-Cheng Lu; Yung-ho Chiu; Chih-Yu Yang; Tai-Yu Lin (Environmental Geochemistry and Health, 2021)

Streptococcus vaginalis sp. nov., a novel bacterial species isolated from vaginal swabs of a pregnant woman with diabetes - An-Shine Chao; Chiao-Yun Lin; Angel Chao; Yun-Shien Lee; Yu-Chung Chang; Hui-Chung Wu; Yu-Jie Dai; Wei-Qi Liao; Fan-Ching Kao; Yi-Sheng Chen (Archives of Microbiology, 2021)

Viable and Heat-Killed Probiotic Strains Improve Oral Immunity by Elevating the IgA Concentration in the Oral Mucosa - Wen-Yang Lin; Yi-Wei Kuo; Ching-Wei Chen; Yu-Fen Huang; Chen-Hung Hsu; Jia-Hung Lin; Cheng-Ruei Liu; Jui-Fen Chen; Ko-Chiang Hsia; Hsieh-Hsun Ho (Current Microbiology, 2021)
Oral-nasal mucosal immunity plays a crucial role in protecting the body against bacterial and viral invasion. Safe probiotic products have been used to enhance human immunity and oral health. In this study, we verified the beneficial effects of mixed viable probiotic tablets, consisting of Lactobacillus salivarius subsp. salicinius AP-32, Bifidobacterium animalis subsp. lactis CP-9, and Lactobacillus paracasei ET-66, and heat-killed probiotic tablets, consisting of L. salivarius subsp. salicinius AP-32 and L. paracasei ET-66, on oral immunity among 45 healthy participants. Participants were randomly divided into viable probiotic, heat-killed probiotic, and placebo groups. The administration of treatment lasted for 4 weeks. Saliva samples were collected at Weeks 0, 2, 4, and 6, and Lactobacillus , Bifidobacterium and Streptococcus mutans populations and IgA concentration were measured. IgA concentrations, levels of TGF-beta and IL-10 in PBMCs cells were quantified by ELISA method. Results showed that salivary IgA levels were significantly increased on administration of both the viable (119.30 ± 12.63%, *** P < 0.001) and heat-killed (116.78 ± 12.28%, *** P < 0.001) probiotics for 4 weeks. Among three probiotic strains, AP-32 would effectively increase the levels of TGF-beta and IL-10 in PBMCs. The oral pathogen Streptococcus mutans was significantly reduced on viable probiotic tablet administration (49.60 ± 31.01%, *** P < 0.001). The in vitro antibacterial test confirmed that viable probiotics effectively limited the survival rate of oral pathogens. Thus, this clinical pilot study demonstrated that oral probiotic tablets both in viable form or heat-killed form could exert beneficial effects on oral immunity via IL-10, TGB-beta mediated IgA secretion. The effective dosage of viable probiotic content in the oral tablet was 10 9 CFUs/g and the heat-killed oral tablet was 1 × 10 10 cells/g.

Dating deformation using sheared leucogranite: temporal constraints by 40Ar/39Ar thermochronology for the Mae Ping shear zone, NW Thailand - Yu-Ling Lin; Tung-Yi Lee; Ching-Hua Lo; Sarah C. Sherlock; Yoshiyuki Iizuka; Tadashi Usuki; Long Xiang Quek; Punya Charusiri (Contributions to Mineralogy and Petrology, 2021)

Anti-Inflammatory and anti-proliferative oleanane-type triterpene glycosides from the vine of Momordica cochinchinensis - Hung-Tse Huang; Yu-Chi Lin; Li-Jie Zhang; Chia-Ching Liaw; Hsin-Yen Chen; Ming-Tung Hsueh; Yao-Haur Kuo (Natural Product Research, 2021)

Germination dynamics of allergenic fungal spores in respiratory mucus - Wan-Rou Lin; Szu-Yu Chen; Shih-Ching Hsiao; Pi-Han Wang (Aerobiologia, 2021)

The Effect of Wave-Induced Current and Coastal Structure on Sediment Transport at the Zengwen River Mouth - Chun-Hung Pao; Jia-Lin Chen; Shih-Feng Su; Yu-Ching Huang; Wen-Hsin Huang; Chien-Hung Kuo (Journal of Marine Science and Engineering, 2021)
The mechanisms that control estuarine sediment transport are complicated due to the interaction between riverine flows, tidal currents, waves, and wave-driven currents. In the past decade, severe seabed erosion and shoreline retreat along the sandy coast of western Taiwan have raised concerns regarding the sustainability of coastal structures. In this study, ADCPs (Acoustic Doppler Current Profiler) and turbidity meters were deployed at the mouth of the Zengwen river to obtain the time series and the spatial distribution of flow velocities and turbidity during the base flow and flood conditions. A nearshore circulation model, SHORECIRC, has been adapted into a hybrid finite-difference/finite-volume, TVD (Total Variation Diminishing)-type scheme and coupled with the wave-spectrum model Simulating Waves Nearshore (SWAN). Conventional finite-difference schemes often produce unphysical oscillations when modeling coastal processes with abrupt bathymetric changes at river mouths. In contrast, the TVD-type finite volume scheme allows for robust treatment of discontinuities through the shock-capturing mechanism. The model reproduces water levels, waves, currents observed at the mouth of the Zengwen River reasonably well. The simulated residual sediment transport patterns demonstrate that the transport process at the river mouth is dominated by the interaction of the bathymetry and wave-induced currents when the riverine discharge was kept in reservoirs. The offshore residual transport causes erosion at the northern part of the river mouth, and the onshore residual transport causes accretion in the ebb tidal shoals around the center of the river mouth. The simulated morphological evolution displays significant changes on shallower deltas. The location with significant sea bed changes is consistent with the spot in which severe erosion occurred in recent years. Further analysis of morphological evolution is also discussed to identify the role of coastal structures, for example, the extension of the newly constructed groins near the river mouth.

Shallow gas hydrates off southwest Taiwan and their mechanisms - Yin-Sheng Huang; Shu-Kun Hsu; Chih-Chieh Su; Andrew Tien-Shun Lin; Pai-Sen Yu; Nathalie Babonneau; Gueorgui Ratzov; Serge Lallemand; Pi-Chuen Huang; Shiao-Shan Lin; Jing-Yi Lin; Kuo-Yen Wei; et al. (Marine Geophysical Research, 2021)
We have collected two shallow gas hydrate samples at two sites having different geological settings off southwest Taiwan during the cruise MD214 in 2018. The first core site, MD18-3542, is on the South Yuan-An East Ridge at ~ 1200 m water deep, where a structural unconformity covered by fine-silt sediments appears at ~ 5.5 m below the seafloor. The second core site, MD18-3543, is close to the Good-Weather Ridge at ~ 1100 m water deep, where a gas-related pockmark structure and authigenic carbonates are present at shallow strata with fine-silt sediments near the seafloor. Sediment properties of core MD18-3542 are distinctively different above and below the layer corresponding to the unconformity. Both cores show obvious gaps or voids in the lower core halves. The core features could be linked to the dissociated methane upward migrating from deep strata. Core site settings with upwelling methane would favor the formation of shallow gas hydrates. At site MD18-3542, the shallow hydrate could be formed due to high concentration methane kept beneath the unconformity covered by fine-silt sediments. At site MD18-3543, the shallow hydrate could be formed due to an extremely high flux of upwelling methane trapped either beneath the authigenic carbonates or fine-silt sediments.

Continental shelf morphology controlled by bottom currents, mud diapirism, and submarine slumping to the east of the Gaoping Canyon, off SW Taiwan - Yi-Ching Yeh; Chung-Lin Tsai; Shu-Kun Hsu; Hsiao-Shan Lin; Kuan-Ting Chen; Yen-Yu Cho; Chin-Wei Liang (Geo-Marine Letters, 2021)

Correction to: 4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay‑Huyen Chen; Ping‑Chen Shih; Han‑Yu Lin; Po‑Kai Wang; Po‑Ting Pan; Ching‑Wei Chuang; Ming‑Chang Kao (Inflammopharmacology, 2020)

Overexpression of a multifunctional β-glucosidase gene from thermophilic archaeon Sulfolobus solfataricus in transgenic tobacco could facilitate glucose release and its use as a reporter - Chih-Hao Huang; Tzu-Ling Huang; Yu-Chang Liu; Ting-Chieh Chen; Shih-Ming Lin; Shyh-Yu Shaw; Ching-Chun Chang (Transgenic Research, 2020)

A new macrocyclic diterpenoid from Anisomeles indica - Chen-Liang Chao; Hui-Chi Huang; Hsiou-Yu Ding; Jenn-Haung Lai; Hang-Ching Lin; Wen-Liang Chang (Natural Product Research, 2020)

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Targeting Inflammation, PHA-767491 Shows a Broad Spectrum in Protein Aggregation Diseases - Yu-Han Chung; Chia-Wei Lin; Hsin-Yu Huang; Shu-Ling Chen; Hei-Jen Huang; Ying-Chieh Sun; Guan-Chiun Lee; Guey-Jen Lee-Chen; Ya-Ching Chang; Hsiu Mei Hsieh-Li (Journal of Molecular Neuroscience, 2020)

Acute physiological responses to combined blood flow restriction and low-level laser - Yi-Ching Chen; Yu-Han Su; Yen-Ting Lin; Chien-Chun Huang; Ing-Shiou Hwang (European Journal of Applied Physiology, 2020)

Prior Antiplatelet Therapy, Excluding Phosphodiesterase Inhibitor Is Associated with Poor Outcome in Patients with Spontaneous Intracerebral Haemorrhage - Zhuo-Hao Liu; Chi-Hung Liu; Po-Hsun Tu; Ping K. Yip; Ching-Chang Chen; Yu-Chi Wang; Nan-Yu Chen; Yu-Sheng Lin (Translational Stroke Research, 2020)

Integrating Patient-Specific Electrocardiogram Signals and Image-Based Computational Fluid Dynamics Method to Analyze Coronary Blood Flow in Patients during Cardiac Arrhythmias - Szu-Hsien Chou; Kuan-Yu Lin; Zhen-Ye Chen; Chun-Jung Juan; Chien-Yi Ho; Tzu-Ching Shih (Journal of Medical and Biological Engineering, 2020)
Purpose The aim of this study was to use the computational fluid dynamics (CFD) method, patient-specific electrocardiogram (ECG) signals, and computed tomography three-dimensional image reconstruction technique to investigate the blood flow in coronary arteries during cardiac arrhythmia. Methods Two patients with premature ventricular contraction-type cardiac arrhythmia and one with atrial fibrillation-type cardiac arrhythmia were investigated. The inlet velocity of the coronary artery in simulation was applied with the measured velocity profile of the left ventricular outflow tract (LVOT) from the Doppler echocardiography. The measured patient central aortic blood pressure waveform was employed for the coronary artery outlet in simulation. The no-slip boundary condition was applied to the arterial wall. Results For the patient with irregular cardiac rhythms (Case I), the coronary blood flow rate under the shortened and lengthened cardiac rhythms were 0.66 and 0.96 mL/s, respectively. In Case II, the maximum velocity at the LVOT under a normal heartbeat was found to be 101 cm/s, whereas the average value was 73 cm/s. In Case III, the patient was also diagnosed with a congenital stenosis problem at the myocardial bridge (MCB) at the LAD. The measured blood flow rate at the MCB of the LAD for the three heartbeats in Case III was found to be 0.68, 1.08, and 1.14 mL/s. Conclusion The integration of patient-specific ECG signals and image-based CFD methods can clearly analyze hemodynamic information for patients during cardiac arrhythmia. The cardiac arrhythmia can reduce the blood flow in the coronary arteries.

Population Structure of the World Vegetable Center Mungbean Mini Core Collection and Genome-Wide Association Mapping of Loci Associated with Variation of Seed Coat Luster - Caleb Manamik Breria; Ching Hsiang Hsieh; Jo-Yi Yen; Ramakrishnan Nair; Chen-Yu Lin; Shu-Mei Huang; Thomas J. Noble; Roland Schafleitner (Tropical Plant Biology, 2020)

Pulse Oximetry Monitor Feasible for Early Screening of Obstructive Sleep Apnea (OSA) - Huei-Chen Lin; Chien-Ling Su; Jun-Hui Ong; kun-ling Tsai; Yu-Wen Chen; Cheng-Yu Lin; Ling-Ling Chiang; Ching-Hsia Hung (Journal of Medical and Biological Engineering, 2020)

Cold treatment for guava fruits infested with oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) - Kao W. Lin; Huey L. Lin; Ching C. Shiesh; Yu. L. Hsu; Chih. H. Lin; Su. C. Chen; Wen B. Yeh (Applied Entomology and Zoology, 2020)

Spatiotemporal assessment of mortality attributable to ambient PM2.5 exposure in Taiwan during 2008–2015 - Su-Lun Hwang; Yu-Ching Lin; Kuang-Yu Hsiao; Chieh-Mo Lin; Miao-Ching Chi (Air Quality, Atmosphere & Health, 2020)

Mutational signatures and mutagenic impacts associated with betel quid chewing in oral squamous cell carcinoma - Shih-Chi Su; Lun-Ching Chang; Chiao-Wen Lin; Mu-Kuan Chen; Chun-Ping Yu; Wen-Hung Chung; Shun-Fa Yang (Human Genetics, 2019)

Expression of AHI1 Rescues Amyloidogenic Pathology in Alzheimer’s Disease Model Cells - Lai-Lei Ting; Hsien-Tsung Lu; Shu-Fen Yen; Thi Huong Ngo; Fang-Yu Tu; I-Shih Tsai; Yi-Hua Tsai; Fu-Yen Chang; Xiao-Jiang Li; Shihua Li; Ching-Kuo Lee; Shu-Huei Kao; et al. (Molecular Neurobiology, 2019)

Indication of dynamic neurovascular coupling from inconsistency between EEG and fMRI indices across sleep–wake states - Changwei W. Wu; Pei-Jung Tsai; Sharon Chia-Ju Chen; Chia-Wei Li; Ai-Ling Hsu; Hong-Yi Wu; Yu-Ting Ko; Pai-Chuan Hung; Chun-Yen Chang; Ching-Po Lin; Timothy J. Lane; Chia-Yuen Chen (Sleep and Biological Rhythms, 2019)

4-Phenylbutyric acid protects against vasculitic peripheral neuropathy induced by ischaemia–reperfusion through attenuating endoplasmic reticulum stress - Cay-Huyen Chen; Ping-Chen Shih; Han-Yu Lin; Po-Kai Wang; Po-Ting Pan; Ching-Wei Chuang; Ming-Chang Kao (Inflammopharmacology, 2019)

PARK14 (D331Y) PLA2G6 Causes Early-Onset Degeneration of Substantia Nigra Dopaminergic Neurons by Inducing Mitochondrial Dysfunction, ER Stress, Mitophagy Impairment and Transcriptional Dysregulation in a Knockin Mouse Model - Ching-Chi Chiu; Chin-Song Lu; Yi-Hsin Weng; Ying-Ling Chen; Ying-Zu Huang; Rou-Shayn Chen; Yi-Chuan Cheng; Yin-Cheng Huang; Yu-Chuan Liu; Szu-Chia Lai; Kun-Jun Lin; Yan-Wei Lin; et al. (Molecular Neurobiology, 2019)

Magnesium sulfate inhibits binding of lipopolysaccharide to THP-1 cells by reducing expression of cluster of differentiation 14 - Ya-Ying Chang; Tzu-Yu Lin; Ming-Chang Kao; Tsung-Ying Chen; Ching-Feng Cheng; Chih-Shung Wong; Chun-Jen Huang (Inflammopharmacology, 2019)

Mitochondrial Genetic Diversity of the Freshwater Snail Melanoides tuberculata - Yuh-Wen Chiu; Ye-Chen Gan; Po-Hsun Kuo; Kui-Ching Hsu; Mian-Shin Tan; Yu-Min Ju; Hung-Du Lin (Biochemical Genetics, 2019)

Adenosine Augmentation Evoked by an ENT1 Inhibitor Improves Memory Impairment and Neuronal Plasticity in the APP/PS1 Mouse Model of Alzheimer’s Disease - Chia-Chia Lee; Ching-Pang Chang; Chun-Jung Lin; Hsing-Lin Lai; Yu-Han Kao; Sin-Jhong Cheng; Hui-Mei Chen; Yu-Ping Liao; Emilie Faivre; Luc Buée; David Blum; Jim-Min Fang; et al. (Molecular Neurobiology, 2018)

Pre-treatment with angiotensin-(1–7) inhibits tumor growth via autophagy by downregulating PI3K/Akt/mTOR signaling in human nasopharyngeal carcinoma xenografts - Yu-Tsai Lin; Hung-Chen Wang; Hui-Ching Chuang; Yi-Chiang Hsu; Ming-Yu Yang; Chih-Yen Chien (Journal of Molecular Medicine, 2018)

Tissue Section Image-Based Liver Scar Detection - Yung-Kuan Chan; Ming-Jen Chang; Yi-Wen Hung; Ching-Lin Wang; Chun-Fu Hong; Kwong-Chung Tung; Shyr Shen Yu (Journal of Medical and Biological Engineering, 2018)

Exercise Rehabilitation Attenuates Cognitive Deficits in Rats with Traumatic Brain Injury by Stimulating the Cerebral HSP20/BDNF/TrkB Signalling Axis - Willy Chou; Yu-Fan Liu; Cheng-Hsien Lin; Mao-Tsun Lin; Chi-Chun Chen; Wen-Pin Liu; Ching-Ping Chang; Chung-Ching Chio (Molecular Neurobiology, 2018)

Web-Based Experience Sharing Platform on Medical Device Incidents for Clinical Engineers in Hospitals - Mei-Fen Chen; Cheng-Lun Tsai; Yung-Hsin Chen; Yu-Wen Huang; Cheng-Ning Wu; Ching Chou; Chia-Hung Chien; Pei-Weng Tu; Tsair Kao; Kang-Ping Lin (Journal of Medical and Biological Engineering, 2018)

Occurrence of Emerging Contaminants in Aquaculture Waters: Cross-Contamination between Aquaculture Systems and Surrounding Waters - Webber Wei-Po Lai; Yen-Ching Lin; Yu-Hsiang Wang; Yue Leon Guo; Angela Yu-Chen Lin (Water, Air, & Soil Pollution, 2018)

Regulation of H+-pyrophosphatase by 14-3-3 Proteins from Arabidopsis thaliana - Yu-Di Hsu; Yu-Fen Huang; Yih-Jiuan Pan; Li-Kun Huang; Ya-Yun Liao; Wei-Hua Lin; Tzu-Yin Liu; Ching-Hung Lee; Rong-Long Pan (The Journal of Membrane Biology, 2018)

Improving the management of Taiwanese fishery resource conservation zones based on public perceptions and willingness to pay for ecosystem services - Jyun-Long Chen; Yu-Sheng Lin; Ching-Ta Chuang (Journal of Coastal Conservation, 2018)

Treatment outcome of non-carbapenemase-producing carbapenem-resistant Klebsiella pneumoniae infections: a multicenter study in Taiwan - Chin-Fang Su; Chien Chuang; Yi-Tsung Lin; Yu-Jiun Chan; Jung-Chung Lin; Po-Liang Lu; Ching-Tai Huang; Jann-Tay Wang; Yin-Ching Chuang; L. Kristopher Siu; Chang-Phone Fung (European Journal of Clinical Microbiology & Infectious Diseases, 2018)

Impacts of hydrogeological characteristics on groundwater-level changes induced by earthquakes - Ching-Yi Liu; Yeeping Chia; Po-Yu Chuang; Yung-Chia Chiu; Tai-Lin Tseng (Hydrogeology Journal, 2018)

Seasonal variation and source apportionment of PM2.5-bound trace elements at a coastal area in southwestern Taiwan - Su-Lun Hwang; Miao-Ching Chi; Su-Er Guo; Yu-Ching Lin; Chiang-Ting Chou; Chieh-Mo Lin (Environmental Science and Pollution Research, 2018)

The persistence and photostabilizing characteristics of benzotriazole and 5-methyl-1H-benzotriazole reduce the photochemical behavior of common photosensitizers and organic compounds in aqueous environments - Kenneth Hsien-Yung Chung; Yen-Ching Lin; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

Photolytic degradation of ciprofloxacin in solid and aqueous environments: kinetics, phototransformation pathways, and byproducts - Yen-Ching Lin; Kuan-Wen Hsiao; Angela Yu-Chen Lin (Environmental Science and Pollution Research, 2018)

Prevalence, mechanisms and genetic relatedness of the human pathogenic fungus Aspergillus fumigatus exhibiting resistance to medical azoles in the environment of Taiwan - Hsuan‐Chen Wang; Jui‐Chang Huang; Yong‐Hong Lin; Yu‐Hsin Chen; Ming‐I Hsieh; Pui‐Ching Choi; Hsiu‐Jung Lo; Wei‐Lun Liu; Ching‐Shan Hsu; Hsin‐I Shih; Chi‐Jung Wu; Yee‐Chun Chen (Environmental Microbiology, 2018)
Summary Emerging azole resistance in Aspergillus fumigatus poses a serious threat to human health. This nationwide surveillance study investigated the prevalence and molecular characteristics of azole‐resistant A. fumigatus environmental isolates in Taiwan, an island country with increasing use of azole fungicides. Of the 2760 air and soil samples screened from 2014 to 2016, 451 A. fumigatus isolates were recovered from 266 samples and 34 isolates from 29 samples displayed resistance to medical azoles (itraconazole, voriconazole or posaconazole). The resistance prevalence was 10.9% and 7.5% in A. fumigatus ‐positive samples and isolates respectively. Most (29, 85.3%) azole‐resistant isolates harboured TR 34 /L98H mutations, which were widely distributed, clustered genetically with clinical isolates, and had growth rates that were similar to those of the wild‐type isolates. Microsatellite genotyping revealed both the global spread of the TR 34 /L98H isolates and the occurrence of TR 34 /L98H/S297T/F495I isolates belonging to local microsatellite genotypes. AfuMDR3 and atrF , two efflux transporter genes, were constitutively upregulated in two individual resistant isolates without cyp51A mutations, highlighting their potential roles in azole resistance. These results emphasize the need for periodic environmental surveillance at the molecular level in regions in which azole fungicides are applied, and agricultural fungicide management strategies that generate less selective pressure should be investigated.

Effects of fine particulate matter and its constituents on emergency room visits for asthma in southern Taiwan during 2008–2010: a population-based study - Su-Lun Hwang; Yu-Ching Lin; Chieh-Mo Lin; Kuang-Yu Hsiao (Environmental Science and Pollution Research, 2017)

Cytoplasmic aryl hydrocarbon receptor regulates glycogen synthase kinase 3 beta, accelerates vimentin degradation, and suppresses epithelial–mesenchymal transition in non-small cell lung cancer cells - Ching-Hao Li; Chen-Wei Liu; Chi-Hao Tsai; Yi-Jen Peng; Yu-Hsuan Yang; Po-Lin Liao; Chen-Chen Lee; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2017)

p-Hydroxyacetophenone suppresses nuclear factor-κB-related inflammation in nociceptive and inflammatory animal models - Chang Ching-Wen; Chen Yun-Chieh; Lin Yu-Chin; Peng Wen-Huang (Journal of Natural Medicines, 2017)

Estimation of students’ exposure to metal concentrations from river-dust episodes during 1994–2012 - Hao-Jan Yang; Szu-Chieh Chen; Chiung-Wen Hu; Yi-Chen Chiang; Ching-Tsan Tsai; Pin-Yu Lin; Dian-Jheng Lai; Chung-Yih Kuo (Environmental Science and Pollution Research, 2017)

Beneficial Effect of Astragaloside on Alzheimer’s Disease Condition Using Cultured Primary Cortical Cells Under β-amyloid Exposure - Ching-Ping Chang; Yu-Fan Liu; Hung-Jung Lin; Chien-Chin Hsu; Bor-Chih Cheng; Wen-Pin Liu; Mao-Tsun Lin; Shu-Fen Hsu; Li-Sheng Chang; Kao-Chang Lin (Molecular Neurobiology, 2016)

CLEC5A is critical for dengue virus-induced osteoclast activation and bone homeostasis - Ya-Lang Huang; Szu-Ting Chen; Ren-Shyan Liu; Yen-Hsu Chen; Chun-Yu Lin; Chung-Hao Huang; Pei-Yun Shu; Ching-Len Liao; Shie-Liang Hsieh (Journal of Molecular Medicine, 2016)

A galactopoiesis accordant yield of functional recombinant human factor IX from homozygous transgenic pigs requires a large amount of vitamin K supplementation - Chon-Ho Yen; Tien-Shuh Yang; Yin-Shen Lin; Meng-Hwan Lee; Kuo-Cheng Yu; Chung-Lin Huang; How-Hong Hsieh; Ching-Fu Tu (Transgenic Research, 2016)

Curcumin downregulates p38 MAPK-dependent X-ray repair cross-complement group 1 (XRCC1) expression to enhance cisplatin-induced cytotoxicity in human lung cancer cells - Chun-Liang Tung; Yi-Jun Jian; Jyh-Cheng Chen; Tai-Jing Wang; Wen-Ching Chen; Hao-Yu Zheng; Po-Yuan Chang; Kai-Sheng Liao; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

Molecular Characterization of Ethylene Response Sensor 1 (BoERS1) in Bambusa oldhamii - Yi-Lin Hsieh; Ching-Fang Lu; Bing-Yu Chiang; Shu-Chien Liao; Rita P.-Y. Chen; Choun-Sea Lin; Ai-Yu Wang; Chien-Chih Yang (Plant Molecular Biology Reporter, 2016)

Monsoonal and lunar variability in microzooplankton abundance and community structure in the Terusan mangrove creek (Malaysia) - Yu Lin Yong; Li Lee Chew; Choon Weng Lee; Ving Ching Chong (Marine Biology Research, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Clinical Pedicle Screw Insertion Trials and System Improvement of C-arm Image Navigation System - Chih-Ju Chang; Ching-Hsiao Yu; Geng-Li Lin; Alex Tse; Hong-Yu Chu; Ching-Shiow Tseng (Journal of Medical and Biological Engineering, 2016)

Multiobjective Optimal Design of Sewerage Rehabilitation by Using the Nondominated Sorting Genetic Algorithm-II - Yu-Hao Lin; Yi-Ping Chen; Ming-Der Yang; Tung-Ching Su (Water Resources Management, 2016)

Sphere-formation culture of testicular germ cells in the common marmoset, a small New World monkey - Zachary Yu-Ching Lin; Orie Hikabe; Sadafumi Suzuki; Takamasa Hirano; Haruhiko Siomi; Erika Sasaki; Masanori Imamura; Hideyuki Okano (Primates, 2016)

G206D Mutation of Presenilin-1 Reduces Pen2 Interaction, Increases Aβ42/Aβ40 Ratio and Elevates ER Ca2+ Accumulation - Wei-Ting Chen; Yi-Fang Hsieh; Yan-Jing Huang; Che-Ching Lin; Yen-Tung Lin; Yu-Chao Liu; Cheng-Chang Lien; Irene Han-Juo Cheng (Molecular Neurobiology, 2015)

Parasite and Infected-Erythrocyte Image Segmentation in Stained Blood Smears - Yi-Wen Hung; Ching-Lin Wang; Chuin-Mu Wang; Yung-Kuan Chan; Lin-Yu Tseng; Chiu-Wen Lee; Kwong-Chung Tung (Journal of Medical and Biological Engineering, 2015)

Intra-Colonial Functional Differentiation-Related Modulation of the Cellular Membrane in a Pocilloporid Coral Seriatopora caliendrum - Chuan-Ho Tang; Ping-Chang Ku; Ching-Yu Lin; Te-Hao Chen; Kuo-Hsin Lee; Shu-Hui Lee; Wei-Hsien Wang (Marine Biotechnology, 2015)

Associations between TRPV4 genotypes and body mass index in Taiwanese subjects - De-Min Duan; Semon Wu; Lung-An Hsu; Ming-Sheng Teng; Jeng-Feng Lin; Yu-Chen Sun; Ching-Feng Cheng; Yu-Lin Ko (Molecular Genetics and Genomics, 2015)

Metabolites of Scutellariae Radix Inhibit Injury of Endothelial Cells in Hypoxia Device - Chia-Lun Chao; Shiuan-Pey Lin; Yu-Chi Hou; Pei-Dawn Lee Chao; Nen-Chung Chang; Yu-Ching Huang; Feng-Ming Ho (Journal of Medical and Biological Engineering, 2015)

The differential roles of Slit2-exon 15 splicing variants in angiogenesis and HUVEC permeability - Yun-Chiu Yang; Pei-Ni Chen; Siou-Yu Wang; Chen-Yi Liao; Yu-Ying Lin; Shih-Rhong Sun; Chun-Ling Chiu; Yih-Shou Hsieh; Jia-Ching Shieh; Jinghua Tsai Chang (Angiogenesis, 2015)

Occurrence of pharmaceuticals, hormones, and perfluorinated compounds in groundwater in Taiwan - Yen-Ching Lin; Webber Wei-Po Lai; Hsin-hsin Tung; Angela Yu-Chen Lin (Environmental Monitoring and Assessment, 2015)

Analysis of space–time patterns of rainfall events during 1996–2008 in Yilan County (Taiwan) - Hwa-Lung Yu; Bo-Lin Chen; Chuan-Hung Chiu; Mong-Ming Lu; Ching-pin Tung (Stochastic Environmental Research and Risk Assessment, 2015)

Methodology of disaster risk assessment for debris flows in a river basin - Ing-Jia Chiou; Ching-Ho Chen; Wei-Lin Liu; Shiao-Mei Huang; Yu-Min Chang (Stochastic Environmental Research and Risk Assessment, 2015)

Is abnormal non-high-density lipoprotein cholesterol a gender-specific predictor for metabolic syndrome in patients with schizophrenia taking second-generation antipsychotics? - Esther Ching-Lan Lin; Wen-Chuan Shao; Hsin-Ju Yang; Miaofen Yen; Sheng-Yu Lee; Pei-Chun Wu; Ru-Band Lu (Metabolic Brain Disease, 2015)

The Akt inhibitor MK-2206 enhances the cytotoxicity of paclitaxel (Taxol) and cisplatin in ovarian cancer cells - Ying-Hsi Lin; Bert Yu-Hung Chen; Wei-Ting Lai; Shao-Fu Wu; Jih-Hwa Guh; Ann-Lii Cheng; Lih-Ching Hsu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2015)

Allyl isothiocyanate (AITC) inhibits pregnane X receptor (PXR) and constitutive androstane receptor (CAR) activation and protects against acetaminophen- and amiodarone-induced cytotoxicity - Yun-Ping Lim; Ching-Hao Cheng; Wei-Cheng Chen; Shih-Yu Chang; Dong-Zong Hung; Jih-Jung Chen; Lei Wan; Wei-Chih Ma; Yu-Hsien Lin; Cing-Yu Chen; Tsuyoshi Yokoi; Miki Nakajima; et al. (Archives of Toxicology, 2015)

The development of stream temperature model in a mountainous river of Taiwan - Ching-Pin Tung; Tsung-Yu Lee; Jr-Chuang Huang; Po-Wen Perng; Shih-Ji Kao; Lin-Yen Liao (Environmental Monitoring and Assessment, 2014)

Association Study Between Macrophage Migration Inhibitory Factor-173 Polymorphism and Acute Myeloid Leukemia in Taiwan - Latha Ramireddy; Chien-Yu Lin; Su-Ching Liu; Wan-Yu Lo; Rouh-Mei Hu; Yi-Chin Peng; Ching-Tien Peng (Cell Biochemistry and Biophysics, 2014)

Spatial distribution of soil erosion and suspended sediment transport rate for Chou-Shui river basin - Chin-Ping Lin; Ching-Nuo Chen; Yu-Min Wang; Chih-Heng Tsai; Chang-Tai Tsai (Journal of Earth System Science, 2014)

Maintenance of human adipose derived stem cell (hASC) differentiation capabilities using a 3D culture - Ching-Yu Lin; Chi-Hui Huang; Yuan-Kun Wu; Nai-Chen Cheng; Jiashing Yu (Biotechnology Letters, 2014)

Nanomolar Naloxone Attenuates Neurotoxicity Induced by Oxidative Stress and Survival Motor Neuron Protein Deficiency - Ya-Yun Hsu; Yuh-Jyh Jong; Yu-Ting Lin; Yu-Ting Tseng; Shih-Hsien Hsu; Yi-Ching Lo (Neurotoxicity Research, 2014)

Functional Investigation of Transmembrane Helix 3 in H+-Translocating Pyrophosphatase - Ching-Hung Lee; Yen-Wei Chen; Yun-Tzu Huang; Yih-Jiuan Pan; Chien-Hsien Lee; Shih-Ming Lin; Lin-Kun Huang; Yueh-Yu Lo; Yu-Fen Huang; Yu-Di Hsu; Shih-Chung Yen; Jenn-Kang Hwang; et al. (The Journal of Membrane Biology, 2013)

Pemetrexed downregulates ERCC1 expression and enhances cytotoxicity effected by resveratrol in human nonsmall cell lung cancer cells - Ruey-Shyang Chen; Jen-Chung Ko; Hsien-Chun Chiu; Ting-Yu Wo; Yi-Jhen Huang; Sheng-Chieh Tseng; Huang-Jen Chen; Yu-Ching Huang; Yi-Jun Jian; Wei-Ting Lee; Yun-Wei Lin (Naunyn-Schmiedeberg's Archives of Pharmacology, 2013)

Minocycline accelerates hypoxia-inducible factor-1 alpha degradation and inhibits hypoxia-induced neovasculogenesis through prolyl hydroxylase, von Hippel–Lindau-dependent pathway - Ching-Hao Li; Po-Lin Liao; Ya-Ting Yang; Shih-Hsuan Huang; Cheng-Hui Lin; Yu-Wen Cheng; Jaw-Jou Kang (Archives of Toxicology, 2013)

Design, synthesis, and evaluation of fluorescent cell-penetrating peptidic antagonists of Grb2-SH2 for targeting MCF-7 breast cancer cells - Yu-Cheng Hsiao; Chen-Yu Lee; Yi-Jhen Lin; Shu-Huai Tsai; Kee-Ching G. Jeng; Wei-Ting Chao; Feng-Di T. Lung (Medicinal Chemistry Research, 2013)

Hyperinakin, a new anti-inflammatory phloroglucinol derivative from Hypericum nakamurai - Yuan-Bin Cheng; Ahmed Eid Fazary; Yu-Chi Lin; I-Wen Lo; Seow-Chin Ong; Shun-Ying Chen; Ching-Te Chien; Yen-Jung Lin; Wan-Wan Lin; Ya-Ching Shen (Natural Product Research, 2013)

Computer Aided Alignment and Quantitative 4D Structural Plasticity Analysis of Neurons - Ping-Chang Lee; Hai-yan He; Chih-Yang Lin; Yu-Tai Ching; Hollis T. Cline (Neuroinformatics, 2013)

The enhancement of biofilm formation in Group B streptococcal isolates at vaginal pH - Yueh-Ren Ho; Chien-Ming Li; Chen-Hsiang Yu; Yuh-Jyh Lin; Ching-Ming Wu; I-Chen Harn; Ming-Jer Tang; Yi-Ting Chen; Fang-Chi Shen; Chien-Yi Lu; Tai-Chun Tsai; Jiunn-Jong Wu (Medical Microbiology and Immunology, 2013)

Composition and Distribution of Elements and Ultrastructural Topography of a Human Cardiac Calculus - Ching-Li Cheng; Hsiao-Huang Chang; Pei-Jung Huang; Yu-Ting Chu; Shan-Yang Lin (Biological Trace Element Research, 2013)

A study of the frequency of methylation of gene promoter regions in colorectal cancer in the Taiwanese population - CHANG-CHIEH WU; JEN-CHUN KUAN; CHIH-HSIUNG HSU; TZU-AN CHEN; CHIEN-AN SUN; TSAN YANG; SHINN-LONG LIN; YU-CHING CHOU (Journal of Genetics, 2013)

Glycogen synthase kinase-3β inactivation is an intracellular marker and regulator for endotoxemic neutrophilia - Tsan-Tzu Yang; Chia-Ling Chen; Wei-Chieh Lin; Yee-Shin Lin; Po-Chun Tseng; Chia-Yuan Hsieh; Yu-Hong Chen; Wei-Ching Huang; Cheng-Chieh Tsai; Chi-Yun Wang; Chi-Chang Shieh; Chiou-Feng Lin (Journal of Molecular Medicine, 2013)

A molecular diagnosis method using real-time PCR for quantification and detection of Fusarium oxysporum f. sp. cubense race 4 - Ying-Hong Lin; Ching-Chung Su; Chih-Ping Chao; Chi-Yu Chen; Chung-Jan Chang; Jenn-Wen Huang; Pi-Fang Linda Chang (European Journal of Plant Pathology, 2013)

Recombined sequences between the non-coding control regions of JC and BK viruses found in the urine of a renal transplantation patient - Yu-Ching Liaw; Cheng-Hsu Chen; Kuo-Hsiung Shu; Chiung-Yao Fang; Wei-Chih Ou; Pei-Lain Chen; Cheng-Huang Shen; Mien-Chun Lin; Deching Chang; Meilin Wang (Virus Genes, 2012)

Albumin prevents reactive oxygen species-induced mitochondrial damage, autophagy, and apoptosis during serum starvation - Shu-Yu Liu; Chia-Ling Chen; Tsan-Tzu Yang; Wei-Ching Huang; Chia-Yuan Hsieh; Wan-Jou Shen; Tsung-Ting Tsai; Chi-Chang Shieh; Chiou-Feng Lin (Apoptosis, 2012)

In vivo screening of zebrafish microRNA responses to bacterial infection and their possible roles in regulating immune response genes after lipopolysaccharide stimulation - Tsung-Han Wu; Chieh-Yu Pan; Ming-Ching Lin; Jung-Chen Hsieh; Cho-Fat Hui; Jyh-Yih Chen (Fish Physiology and Biochemistry, 2012)

Development of transgenic watermelon resistant to Cucumber mosaic virus and Watermelon mosaic virus by using a single chimeric transgene construct - Ching-Yi Lin; Hsin-Mei Ku; Yi-Hua Chiang; Hsiu-Yin Ho; Tsong-Ann Yu; Fuh-Jyh Jan (Transgenic Research, 2012)

Interplay of RsbM and RsbK controls the σ B activity of Bacillus cereus - Lei‐Chin Chen; Jung‐Chi Chen; Jwu‐Ching Shu; Chien‐Yen Chen; Ssu‐Ching Chen; Shu‐Hwa Chen; Chun‐Yen Lin; Chi‐Yu Lu; Chien‐Cheng Chen (Environmental Microbiology, 2012)
Summary The alternative transcription factor σ B of Bacillus cereus controls the expression of a number of genes that respond to environmental stress. Four proteins encoded in the sigB gene cluster, including RsbV, RsbW, RsbY (RsbU) and RsbK, are known to be essential in the σ B ‐mediated stress response. In the context of stress, the hybrid sensor kinase RsbK is thought to phosphorylate the response regulator RsbY, a PP2C serine phosphatase, leading to the dephosphorylation of the phosphorylated RsbV. The unphosphorylated RsbV then sequesters the σ B antagonist, RsbW, ultimately liberating σ B . The gene arrangement reveals an open reading frame, bc1007 , flanked immediately downstream by rsbK within the sigB gene cluster. However, little is known about the function of bc1007 . In this study, the deletion of bc1007 resulted in high constitutive σ B expression independent of environmental stimuli, indicating that bc1007 plays a role in σ B regulation. A bacterial two‐hybrid analysis demonstrated that BC1007 interacts directly with RsbK, and autoradiographic studies revealed a specific C 14 ‐methyl transfer from the radiolabelled S‐adenosylmethionine to RsbK when RsbK was incubated with purified BC1007. Our data suggest that BC1007 (RsbM) negatively regulates σ B activity by methylating RsbK. Additionally, mutagenic substitution was employed to modify 12 predicted methylation residues in RsbK. Certain RsbK mutants were able to rescue σ B activation in a rsbK ‐deleted bacterial strain, but RsbK E439A failed to activate σ B , and RsbK E446A only moderately induced σ B . These results suggest that Glu439 is the preferred methylation site and that Glu446 is potentially a minor methylation site. Gene arrays of the rsbK orthologues and the neighbouring rsbM orthologues are found in a wide range of bacteria. The regulation of sigma factors through metylation of RsbK‐like sensor kinases appears to be widespread in the microbial world.

Identification of secretory gelsolin as a plasma biomarker associated with distant organ metastasis of colorectal cancer - Ming-Hung Tsai; Chih-Ching Wu; Pei-Hua Peng; Ying Liang; Yung-Chin Hsiao; Kun-Yi Chien; Jeng-Ting Chen; Shin-Jie Lin; Rei-Ping Tang; Ling-Ling Hsieh; Jau-Song Yu (Journal of Molecular Medicine, 2012)

In vitro shoot induction and plant regeneration from flower buds in Paphiopedilum orchids - Yu-Ju Liao; Yu-Ching Tsai; Yung-Wei Sun; Ruey-Song Lin; Fang-Sheng Wu (In Vitro Cellular & Developmental Biology - Plant, 2011)

Infectious bursal disease DNA vaccination conferring protection by delayed appearance and rapid clearance of invading viruses - Yung-Yi Chen; Ming Kun Hsieh; Chun-Yu Tung; Ching Ching Wu; Tsang Long Lin (Archives of Virology, 2011)

Nitric oxide activates superoxide dismutase and ascorbate peroxidase to repress the cell death induced by wounding - Chih-Ching Lin; Pei-Ju Jih; Hsin-Hung Lin; Jeng-Shane Lin; Ling-Lan Chang; Yu-Hsing Shen; Shih-Tong Jeng (Plant Molecular Biology, 2011)

Assessing abalone growth inhibition risk to cadmium and silver by linking toxicokinetics/toxicodynamics and subcellular partitioning - Wei-Yu Chen; Yun-Ru Ju; Bo-Ching Chen; Jeng-Wei Tsai; Chia-Jung Lin; Chung-Min Liao (Ecotoxicology, 2011)

Lipopolysaccharide-stimulated activation of murine DC2.4 cells is attenuated by n-butylidenephthalide through suppression of the NF-κB pathway - Ru-Huei Fu; Horng-Jyh Hran; Ching-Liang Chu; Chin-Mao Huang; Shih-Ping Liu; Yu-Chi Wang; Ya-Hsien Lin; Woei-Cherng Shyu; Shinn-Zong Lin (Biotechnology Letters, 2011)

Molecular epidemiology of Echovirus 30 in Taiwan, 1988–2008 - Guan-Ming Ke; Kuei-Hsiang Lin; Po-Liang Lu; Yi-Chin Tung; Chu-Feng Wang; Liang-Yin Ke; Min-Sheng Lee; Pei-Chin Lin; Hui-Ju Su; Yi-Ying Lin; Tzu-Ping Huang; Jen-Ren Wang; et al. (Virus Genes, 2011)

Association between human papillomavirus and adenocarcinoma of rectum and recto-sigmoid junction: a cohort study of 10,612 women in Taiwan - Li-Chung Chuang; Hui-Chi Chen; San-Lin You; Ching-Yu Lin; Mei-Hung Pan; Yi-Chun Chou; Chang-Yao Hsieh; Chien-Jen Chen (Cancer Causes & Control, 2010)

Constitutive expression of a fungal glucose oxidase gene in transgenic tobacco confers chilling tolerance through the activation of antioxidative defence system - Subbiyan Maruthasalam; Yi Lun Liu; Ching Mei Sun; Pei Ying Chen; Chih Wen Yu; Pei Fang Lee; Chin Ho Lin (Plant Cell Reports, 2010)

Bacterial community of very wet and acidic subalpine forest and fire-induced grassland soils - Yu-Te Lin; Ching-Ping Lin; Shu-Miaw Chaw; William B. Whitman; David C. Coleman; Chih-Yu Chiu (Plant and Soil, 2010)

Involvement of the residues of GSKIP, AxinGID, and FRATtide in their binding with GSK3β to unravel a novel C-terminal scaffold-binding region - Shen-Long Howng; Chi-Ching Hwang; Chia-Yi Hsu; Meng-Yu Hsu; Chun-Yen Teng; Chia-Hua Chou; Mei-Feng Lee; Chia-Hung Wu; Shean-Jaw Chiou; Ann-Shung Lieu; Joon-Khim Loh; Chia-Ning Yang; et al. (Molecular and Cellular Biochemistry, 2010)

Porcine lactoferrin as feedstuff additive elevates avian immunity and potentiates vaccination - Che-Ming Hung; Shinn-Chih Wu; Chih-Ching Yen; Ming-Fong Lin; Yi-Wen Lai; Yu-Tang Tung; Hsiao-Ling Chen; Chuan-Mu Chen (BioMetals, 2010)

Probiotic Lactobacillus casei Expressing Human Lactoferrin Elevates Antibacterial Activity in the Gastrointestinal Tract - Hsiao-Ling Chen; Yi-Wen Lai; Chua-Shun Chen; Te-Wei Chu; Willie Lin; Chih-Ching Yen; Ming-Fong Lin; Ming-Yu Tu; Chuan-Mu Chen (BioMetals, 2010)

Regeneration of soybean (Glycine max L. Merrill) through direct somatic embryogenesis from the immature embryonic shoot tip - Murugan Loganathan; Subbiyan Maruthasalam; Ling Yin Shiu; Wei Ching Lien; Wen Hwei Hsu; Pei Fang Lee; Chih Wen Yu; Chin Ho Lin (In Vitro Cellular & Developmental Biology - Plant, 2010)

Rigorous pulse detection from full-waveform airborne laser scanning data - Yu-Ching Lin; J. P. Mills; S. Smith-Voysey (International Journal of Remote Sensing, 2010)

Ploidy doubling by in vitro culture of excised protocorms or protocorm-like bodies in Phalaenopsis species - Wen Huei Chen; Ching Yan Tang; Yu Lin Kao (Plant Cell, Tissue and Organ Culture (PCTOC), 2009)

The Mandibular Cartilage Metabolism is Altered by Damaged Subchondral Bone from Traumatic Impact Loading - Yu-Yu Lin; Nobuaki Tanaka; Satoru Ohkuma; Takashi Kamiya; Ryo Kunimatsu; Yu-Ching Huang; Motoko Yoshioka; Tomomi Mitsuyoshi; Yuki Tanne; Kotaro Tanimoto; Eiji Tanaka; Kazuo Tanne (Annals of Biomedical Engineering, 2009)

Recombinant ORF66 and ORFK12 antigens for the detection of human herpesvirus 8 antibodies in HIV-positive and -negative patients - Tsuey-Ching Yang; Chun-Pin Chang; Yu-Ching Lan; Chao-Li Liu; Mu-Chin Shih; Fang-Yang Wu; Cheng-Wen Lin (Biotechnology Letters, 2009)

Development of a Methodology for Strategic Environmental Assessment: Application to the Assessment of Golf Course Installation Policy in Taiwan - Ching-Ho Chen; Ray-Shyan Wu; Wei-Lin Liu; Wen-Ray Su; Yu-Min Chang (Environmental Management, 2009)

Characteristics analysis for the flash flood-induced debris flows - Chen Chien-Yuan; Chen Lien-Kuang; Yu Fan-Chieh; Lin Sheng-Chi; Lin Yu-Ching; Lee Chou-Lung; Wang Yu-Ting; Cheung Kei-Wai (Natural Hazards, 2008)

Time to rehospitalization in patients with bipolar I disorder on lithium or valproate with adjunctive antipsychotics - Ching-Hua Lin; Ching-Wen Huang; Cheng-Chung Chen; Yu-Fen Hsu; Wen-Ho Chang; Hsien-Yuan Lane (Psychopharmacology, 2008)

Gene expression variation increase in trisomy 21 tissues - Ching Yu Chou; Li Yu Liu; Chien Yu Chen; Cheng Hsien Tsai; Hsiao Lin Hwa; Li Yun Chang; Yi Shing Lin; Fon Jou Hsieh (Mammalian Genome, 2008)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

Lignans and anthraquinones from the fruits of Morinda citrifolia - Chwan Fwu Lin; Ching Li Ni; Yu Ling Huang; Shuenn Jyi Sheu; Chien Chih Chen (Natural Product Research, 2007)

A rice phenomics study—phenotype scoring and seed propagation of a T-DNA insertion-induced rice mutant population - Chyr-Guan Chern; Ming-Jen Fan; Su-May Yu; Ai-Ling Hour; Po-Chang Lu; Yao-Cheng Lin; Fu-Jin Wei; Sheng-Chung Huang; Shu Chen; Ming-Hsing Lai; Ching-Shan Tseng; Hsing-Mu Yen; et al. (Plant Molecular Biology, 2007)

Development of a molecular marker for a bruchid (Callosobruchus chinensis L.) resistance gene in mungbean - Huei-Mei Chen; Chien-An Liu; C. George Kuo; Ching-Mei Chien; Horng-Chi Sun; Chung-Chu Huang; Yu-Chung Lin; Hsin-Mei Ku (Euphytica, 2007)

Solubilization of inorganic phosphates and plant growth promotion by Aspergillus niger - Chun-Chao Chuang; Yu-Lin Kuo; Chen-Ching Chao; Wei-Liang Chao (Biology and Fertility of Soils, 2007)

A web-based decision support system for slopeland hazard warning - Yu Fan-Chieh; Chen Chien-Yuan; Lin Sheng-Chi; Lin Yu-Ching; Wu Shang-Yu; Cheung Kei-Wai (Environmental Monitoring and Assessment, 2007)

A rice gene activation/knockout mutant resource for high throughput functional genomics - Yue-Ie Hsing; Chyr-Guan Chern; Ming-Jen Fan; Po-Chang Lu; Ku-Ting Chen; Shuen-Fang Lo; Peng-Kai Sun; Shin-Lon Ho; Kuo-Wei Lee; Yi-Chieh Wang; Wen-Lii Huang; Swee-Suak Ko; et al. (Plant Molecular Biology, 2007)

Improving debris flow monitoring in Taiwan by using high-resolution rainfall products from QPESUMS - Chien-Yuan Chen; Lee-Yao Lin; Fan-Chieh Yu; Ching-Sheng Lee; Chun-Chieh Tseng; An-Hsiang Wang; Kei-Wai Cheung (Natural Hazards, 2007)

Induction of G2/M phase arrest and apoptosis by a novel enediyne derivative, THDA, in chronic myeloid leukemia (K562) cells - Zchong-Zcho Wu; Ching-Ming Chien; Sheng-Huei Yang; Yi-Hsiung Lin; Xiu-Wei Hu; Yu-Jhang Lu; Ming-Jung Wu; Shinne-Ren Lin (Molecular and Cellular Biochemistry, 2006)

Organization and promoter analysis of a tiger shrimp Penaeus monodon single WAP domain-containing protein gene - Jyh Yih CHEN; Jian Chyi CHEN; Sheng Hwa LIN; Chia Yu PAN; Ching Ming KUO (Fisheries Science, 2006)

Contrasting phylogeographical patterns of two closely related species, Machilus thunbergii and Machilus kusanoi (Lauraceae), in Taiwan - Su‐Hwa Wu; Ching‐Yuan Hwang; Tsan‐Piao Lin; Jeng‐Der Chung; Yu‐Pin Cheng; Shih‐Ying Hwang (Journal of Biogeography, 2006)
Aim The purpose of this paper was to study the patterns of genetic variation, demographic history, haplotype relationships and potential location of diversity centres of two closely related species, Machilus thunbergii and Machilus kusanoi . Location The phylogeography of M. thunbergii and M. kusanoi was examined by sampling 110 and 106 individuals from 25 and 16 sampling sites, respectively, across their distributional range in Taiwan. Machilus thunbergii is distributed on the Asian mainland, South Korea, southern Japan, the Ryukyus, Taiwan and the Philippines, whereas M. kusanoi is endemic to Taiwan. These two species are closely related, and both are widely distributed in Taiwan but occupy different altitudinal zones and habitats. Methods The range‐wide variation of M. thunbergii and M. kusanoi in Taiwan was studied using chloroplast DNA (cpDNA) variations. A haplotype network was constructed with the computer program tcs . Nested clade analysis was conducted with the computer program ceodis , and various parameters of genetic diversity were calculated and neutrality tested by the computer program D na SP. Population differentiation was estimated using the programs arlequin and hapstep . The contribution of the populations to gene diversity and to allelic richness was calculated using the software contrib . The level of divergence for each population from the remaining populations was calculated as the mean value of pairwise F ST for each population against the rest of the populations. Results Extremely low levels of genetic differentiation were found for both species. This result suggested that these two species probably survived in multiple relict refugia with different population sizes throughout the island during low‐temperature periods of the Pleistocene. In addition, nested clade analysis (NCA) of cpDNA haplotypes indicated that restricted gene flow with isolation‐by‐distance characterized the recolonization after the Pleistocene by Tashueshan and Shiouhluan populations of M. thunbergii in the north‐central area west of the Central Mountain Range (CMR). In contrast, NCA analysis indicated that a major diversity centre on the southern tip of the island (Kending population) and contiguous range expansion characterized the recolonization by M. kusanoi of northern areas along the east side of the CMR. The major diversity centres found for the two species examined were further supported by the results of the mean F ST for individual populations in comparison with other populations, and of the contribution of the divergence component to the total diversity. Main conclusions This research supports the multiple relict refugia hypothesis for both species investigated. Populations of M. thunbergii at Shiouhluan and Tashueshan in the north‐central area west of the CMR represent a diversity centre currently expanding its size. A diversity centre at the southern‐edge population of M. kusanoi , and a contiguous range expansion from Kending, were found. These results indicate that the M. thunbergii populations at Tashueshan and Shiouhluan and the M. kusanoi population at Kending, and even Soukar, are evolutionarily significant units for conservation programmes.

A Natural Compound (Ginsenoside Re) Isolated from Panax ginseng as a Novel Angiogenic Agent for Tissue Regeneration - Ya-Chun Huang; Chiung-Tong Chen; Sung-Ching Chen; Po-Hong Lai; Huang-Chien Liang; Yen Chang; Lin-Chien Yu; Hsing-Wen Sung (Pharmaceutical Research, 2005)

Transgenic tomato plants expressing the Arabidopsis NPR1 gene display enhanced resistance to a spectrum of fungal and bacterial diseases - Wan-Chi Lin; Ching-Fang Lu; Jia-Wei Wu; Ming-Lung Cheng; Yu-Mei Lin; Ning-Sun Yang; Lowell Black; Sylvia K. Green; Jaw-Fen Wang; Chiu-Ping Cheng (Transgenic Research, 2004)

Noninvasive Characterization of Regional Variation in Drug Transport into Human Stratum Corneum in Vivo - Jui-Chen Tsai; Ching-Yu Lin; Hamm-Ming Sheu; Yu-Li Lo; Ying-Hsuan Huang (Pharmaceutical Research, 2003)

Lipid peroxidation and cell death mechanisms in pulmonary epithelial cells induced by peroxynitrite and nitric oxide - Yuan-Soon Ho; Hung-Bin Liou; Jen-Kun Lin; Jiiang-Huei Jeng; Min-Hsiung Pan; Yu-Ping Lin; How-Ran Guo; Sheng-Yow Ho; Ching-Chang Lee; Ying-Jan Wang (Archives of Toxicology, 2002)

Calyculin A Sensitive Protein Phosphatase Is Required for Bacillus anthracis Lethal Toxin Induced Cytotoxicity - Jyh-Hwa Kau; Ching-Gong Lin; Hsin-Hsien Huang; Hui-Ling Hsu; Kuo-Ching Chen; Yu-Ping Wu; Hung-Chi Lin (Current Microbiology, 2002)

Abstracts of presentations on plant protection issues at the xth international congress of virology - E. Ramirez; A. Hernádez; E. Ham; B. L. Barrón; S. W. Ding; W. X. Li; B. J. Shi; R. H. Symons; Q. Li; K. H. Ryu; P. Palukaitis; I. B. Kaplan; et al. (Phytoparasitica, 1997)